Dielectric substrate and method for forming same
The dielectric substrate, featuring a polymer-based core film with a ceramic filler component and a fluoropolymer-based adhesive layer, addresses the challenges of thermomechanical stability and signal loss in copper-clad laminate structures, enhancing performance in high-frequency and high-temperature environments.
Patent Information
- Application Number
- JP2023533286
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-16
- Filing Date
- 2021-12-09
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-12-09
AI Technical Summary
Current dielectric substrates used in copper-clad laminate structures for printed circuit boards face challenges in maintaining thermomechanical stability, resisting high temperatures, and minimizing moisture absorption and electrical signal loss.
A dielectric substrate comprising a polymer-based core film with a resin matrix component and a ceramic filler component, combined with a fluoropolymer-based adhesive layer, where the ceramic filler component has a specific particle size distribution and average particle size to enhance performance.
The proposed dielectric substrate exhibits improved thermomechanical stability, reduced moisture absorption, and lower electrical signal loss, making it suitable for high-frequency applications and extreme temperature conditions.
Smart Images

Figure 0007656041000009 
Figure 0007656041000010 
Figure 0007656041000011
Abstract
Description
[Technical field]
[0001] FIELD OF THE DISCLOSURE This disclosure relates to dielectric substrates and methods of forming same. In particular, this disclosure relates to dielectric substrates for use in copper clad laminate structures and methods of forming same. [Background technology]
[0002] Copper-clad laminates (CCLs) include a dielectric material laminated on or between two layers of conductive copper foil. Subsequent operations convert such CCLs into printed circuit boards (PCBs). When used to form PCBs, the conductive copper foil is selectively etched to form circuits with through-holes that are drilled between layers and metallized, i.e., plated, to establish electrical conductivity between layers in a multilayer PCB. CCLs must therefore exhibit excellent thermomechanical stability. PCBs are also routinely exposed to excessively high temperatures during manufacturing operations, e.g., soldering, as well as during use. As a result, PCBs must function at continuous temperatures in excess of 200°C without deformation and must withstand very large temperature fluctuations while resisting moisture absorption. The dielectric layers of CCLs act as spacers between conductive layers and can minimize electrical signal loss and crosstalk by blocking electrical conductivity. The lower the dielectric constant (dielectric constant) of the dielectric layer, the faster the speed of electrical signals through the layer. Therefore, a low loss factor, which depends on temperature and frequency, as well as the polarizability of the material, is very important for high frequency applications. Accordingly, improved dielectric materials and dielectric layers that can be used in PCBs and other high frequency applications are desired. Summary of the Invention
[0003] According to a first embodiment, the dielectric substrate may include a polymer-based core film and a fluoropolymer-based adhesive layer. The polymer-based core film may include a resin matrix component and a ceramic filler component. The ceramic filler component may include a first filler material. The first filler material may have a particle size distribution of at least about 0.5 micrometers and a D of about 1.6 or less. 10 , D of at least about 0.8 micrometers and not more than about 2.7 micrometers 50 and D of at least about 1.5 micrometers and not more than about 4.7 micrometers 90 may have the following structure:
[0004] According to another aspect, the dielectric substrate may include a polymer-based core film and a fluoropolymer-based adhesive layer. The polymer-based core film may include a resin matrix component and a ceramic filler component. The ceramic filler component may include a first filler material. The first filler material may further have an average particle size of about 10 micrometers or less and a particle size distribution span (PSDS) of about 5 or less, the PSDS being (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler material 90 D is equal to the particle size distribution measurement 10 is the D of the first filler material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler material 50 Equivalent to particle size distribution measurement.
[0005] According to yet another aspect, the dielectric substrate may include a polymer-based core film and a fluoropolymer-based adhesive layer. The polymer-based core film may include a resin matrix component and a ceramic filler component. The ceramic filler component may include a first filler material. The first filler material may have an average particle size of about 10 micrometers or less and a ceramic filler density of about 8.0 micrometers or less. 2 / g or less.
[0006] According to another embodiment, a copper clad laminate may include a copper foil layer and a dielectric substrate overlying the copper foil layer. The dielectric substrate may include a polymer-based core film and a fluoropolymer-based adhesive layer. The polymer-based core film may include a resin matrix component and a ceramic filler component. The ceramic filler component may include a first filler material that may include silica. The first filler material may have a particle size distribution of at least about 0.5 micrometers and a D of about 1.6 or less. 10 , D of at least about 0.8 micrometers and not more than about 2.7 micrometers 50 and D of at least about 1.5 micrometers and not more than about 4.7 micrometers 90 may have the following structure:
[0007] According to yet another aspect, the copper clad laminate may include a copper foil layer and a dielectric substrate overlying the copper foil layer. The dielectric substrate may include a polymer-based core film and a fluoropolymer-based adhesive layer. The polymer-based core film may include a resin matrix component and a ceramic filler component. The ceramic filler component may include a first filler material. The first filler material may further have an average particle size of about 10 micrometers or less and a particle size distribution span (PSDS) of about 5 or less, the PSDS being (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler material 90 D is equal to the particle size distribution measurement 10 is the D of the first filler material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler material 50 Equivalent to particle size distribution measurement.
[0008] According to yet another aspect, a copper clad laminate may include a copper foil layer and a dielectric substrate overlying the copper foil layer. The dielectric substrate may include a polymer-based core film and a fluoropolymer-based adhesive layer. The polymer-based core film may include a resin matrix component and a ceramic filler component. The ceramic filler component may include a first filler material. The first filler material may have an average particle size of about 10 micrometers or less and a ceramic filler density of about 8.0 m. 2 / g or less.
[0009] According to another aspect, a method of forming a dielectric substrate may include combining a resin matrix precursor component and a ceramic filler precursor component to form a forming mixture, forming the forming mixture into a polymer-based core film, and coating the polymer-based core film with a fluoropolymer-based adhesive layer. The ceramic filler precursor component may include a first filler precursor material. The first filler material may have a particle size distribution of at least about 0.5 micrometers and a D of about 1.6 or less. 10 , D of at least about 0.8 micrometers and not more than about 2.7 micrometers 50 and D of at least about 1.5 micrometers and not more than about 4.7 micrometers 90 may have the following structure:
[0010] According to another aspect, a method of forming a dielectric substrate may include combining a resin matrix precursor component and a ceramic filler precursor component to form a forming mixture, forming the forming mixture into a polymeric core film, and coating the polymeric core film with a fluoropolymer adhesive layer. The ceramic filler precursor component may include a first filler precursor material. The first filler precursor material may further have an average particle size of about 10 micrometers or less and a particle size distribution span (PSDS) of about 5 or less, the PSDS being (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler precursor material 90 D is equal to the particle size distribution measurement10 is the D of the first filler precursor material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler precursor material 50 Equivalent to particle size distribution measurement.
[0011] According to yet another aspect, a method of forming a dielectric substrate may include combining a resin matrix precursor component and a ceramic filler precursor component to form a forming mixture, forming the forming mixture into a polymer-based core film, and coating the polymer-based core film with a fluoropolymer-based adhesive layer. The ceramic filler precursor component may include a first filler precursor material. The first filler material may have an average particle size of about 10 micrometers or less and a pore size of about 8.0 micrometers or less. 2 / g or less.
[0012] According to another embodiment, a method of forming a copper clad laminate may include providing a copper foil layer, combining a resin matrix precursor component and a ceramic filler precursor component to form a forming mixture, forming the forming mixture into a polymer-based core film, and providing a fluoropolymer-based adhesive layer between the polymer-based core film and the copper foil. The ceramic filler precursor component may include a first filler precursor material. The first filler material may have a particle size distribution of at least about 0.5 micrometers and a D of about 1.6 or less. 10 , D of at least about 0.8 micrometers and not more than about 2.7 micrometers 50 and D of at least about 1.5 micrometers and not more than about 4.7 micrometers 90 may have the following structure:
[0013] According to yet another aspect, a method of forming a copper clad laminate may include providing a copper foil layer, combining a resin matrix precursor component and a ceramic filler precursor component to form a forming mixture, forming the forming mixture into a polymeric core film, and providing a fluoropolymer adhesive layer between the polymeric core film and the copper foil. The ceramic filler precursor component may include a first filler precursor material. The first filler precursor material may further have an average particle size of about 10 micrometers or less and a particle size distribution span (PSDS) of about 5 or less, the PSDS being (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler precursor material 90 D is equal to the particle size distribution measurement 10 is the D of the first filler precursor material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler precursor material 50 Equivalent to particle size distribution measurement.
[0014] According to yet another aspect, a method of forming a copper clad laminate may include providing a copper foil layer, combining a resin matrix precursor component and a ceramic filler precursor component to form a forming mixture, forming the forming mixture into a polymeric core film, and providing a fluoropolymer adhesive layer between the polymeric core film and the copper foil. The ceramic filler precursor component may include a first filler precursor material. The first filler material may have an average particle size of about 10 micrometers or less and a fluoropolymer adhesive layer of about 8.0 micrometers or less. 2 / g or less. [Brief description of the drawings]
[0015] Embodiments are illustrated by way of example and not limitation in the accompanying figures. [Figure 1] 1 includes diagrams illustrating a method of forming a dielectric layer according to embodiments described herein. [Diagram 2]1 includes diagrams illustrating configurations of dielectric layers formed according to embodiments described herein. [Diagram 3] 1 includes diagrams illustrating a method of forming a copper clad laminate according to embodiments described herein. [Figure 4] 1 includes diagrams illustrating configurations of copper clad laminates formed according to embodiments described herein. [Diagram 5] 1 includes diagrams illustrating a method of forming a printed circuit board according to embodiments described herein. [Figure 6] 1 includes diagrams illustrating configurations of printed circuit boards formed in accordance with embodiments described herein.
[0016] Skilled artisans will appreciate that elements in the figures are illustrated for simplicity and clarity and have not necessarily been drawn to scale. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The following discussion focuses on specific implementations and embodiments of the teachings. The detailed description is provided to help explain the specific embodiments and should not be construed as a limitation on the scope or applicability of the disclosure or teachings. It will be understood that other embodiments can be used based on the disclosure and teachings provided herein.
[0018] The terms "comprises," "comprising," "includes," "including," "has," "having," or any other variations thereof, are intended to cover non-exclusive inclusions. For example, a method, article, or apparatus that includes a list of features is not necessarily limited to only those features, but may include other features not expressly listed or that are inherent to such method, article, or apparatus. Further, unless expressly stated to the contrary, "or" refers to an inclusive or, not an exclusive or. For example, a condition A or B is satisfied by any one of the following: A is true (or present) and B is false (or absent), A is false (or absent) and B is true (or present), and both A and B are true (or present).
[0019] Additionally, the use of "a" or "an" is used to describe elements and components described herein. This is done merely for convenience and to give a general sense of the scope of the invention. This description should be understood as one, at least one, or the singular as including the plural, or vice versa, unless it is clear that this is meant to be otherwise. For example, where a single item is described herein, two or more items can be used in place of the single item. Similarly, where two or more items are described herein, the two or more items can be replaced with a single item.
[0020] The embodiments described herein generally relate to a dielectric substrate that may include a polymer-based core film and a fluoropolymer-based adhesive layer. According to certain embodiments, the polymer-based core film may include a resin matrix component and a ceramic filler component.
[0021] Turning first to the method of forming the dielectric substrate, Figure 1 includes a diagram illustrating a forming method 100 for forming a dielectric substrate according to embodiments described herein. According to certain embodiments, the forming method 100 can include a first step 110 of combining a resin matrix precursor component and a ceramic filler precursor component to form a forming mixture, a second step 120 of forming the forming mixture into a polymer-based core film, and a third step 130 of coating the polymer-based core film with a fluoropolymer-based adhesive layer.
[0022] According to certain embodiments, the ceramic filler precursor composition may include a first filler precursor material that may have particular properties that may improve the performance of the dielectric substrate formed by the forming method 100.
[0023] According to certain embodiments, the first filler precursor material may have a particular size distribution. For purposes of the embodiments described herein, the particle size distribution of a material, e.g., the particle size distribution of a first filler precursor material, is referred to as the particle size distribution D value, D 10 , D 50 and D. 90 Any combination of D from the particle size distribution can be used to describe the 10 The D value is defined as the particle size value below which 10% of the particles are smaller and above which 90% of the particles are larger. 50 The D value is defined as the particle size value below which 50% of the particles are smaller and above which 50% of the particles are larger. 90 A value is defined as the particle size value below which 90% of the particles are smaller and 10% of the particles are greater. For purposes of the embodiments described herein, particle size measurements for certain materials are performed using laser diffraction spectroscopy.
[0024] According to a particular embodiment, the first filler precursor material has a particular size distribution D 10 For example, the D of the first filler precursor material may have a value of 10may be at least about 0.5 micrometers, e.g., at least about 0.6 micrometers, or at least about 0.7 micrometers, or at least about 0.8 micrometers, or at least about 0.9 micrometers, or at least about 1.0 micrometers, or at least about 1.1 micrometers, or even at least about 1.2 micrometers. According to yet other embodiments, the D of the first filler material 10 may be about 1.6 micrometers or less, such as about 1.5 micrometers or less, or even about 1.4 micrometers or less. 10 It will be understood that D may be any value between and including any of the minimum and maximum values listed above. 10 It will be further understood that may be within a range between and including any of the minimum and maximum values recited above.
[0025] According to another embodiment, the first filler precursor material has a particular size distribution D 50 For example, the D of the first filler precursor material may have a value of 50 may be at least about 0.8 micrometers, e.g., at least about 0.9 micrometers, or at least about 1.0 micrometers, or at least about 1.1 micrometers, or at least about 1.2 micrometers, or at least about 1.3 micrometers, or at least about 1.4 micrometers, or at least about 1.5 micrometers, or at least about 1.6 micrometers, or at least about 1.7 micrometers, or at least about 1.8 micrometers, or at least about 1.9 micrometers, or at least about 2.0 micrometers, or at least about 2.1 micrometers, or even at least about 2.2 micrometers. According to yet other embodiments, the D of the first filler material 50D of the first filler precursor material may be about 2.7 micrometers or less, such as about 2.6 micrometers or less, or about 2.5 micrometers or less, or even about 2.4 micrometers or less. 50 It will be understood that D may be any value between and including any of the minimum and maximum values listed above. 50 It will be further understood that may be within a range between and including any of the minimum and maximum values recited above.
[0026] According to another embodiment, the first filler precursor material has a particular size distribution D 90 For example, the D of the first filler precursor material may have a value of 90 may be at least about 1.5 micrometers, e.g., at least about 1.6 micrometers, or at least about 1.7 micrometers, or at least about 1.8 micrometers, or at least about 1.9 micrometers, or at least about 2.0 micrometers, or at least about 2.1 micrometers, or at least about 2.2 micrometers, or at least about 2.3 micrometers, or at least about 2.4 micrometers, or at least about 2.5 micrometers, or at least about 2.6 micrometers, or even at least about 2.7 micrometers. According to yet other embodiments, the D of the first filler material 90 may be about 8.0 micrometers or less, for example, about 7.5 micrometers or less, or about 7.0 micrometers or less, or about 6.5 micrometers or less, or about 6.0 micrometers or less, or about 5.5 micrometers or less, or about 5.4 micrometers or less, or about 5.3 micrometers or less, or about 5.2 micrometers or less, or even about 5.1 micrometers or less. 90 It will be understood that D may be any value between and including any of the minimum and maximum values listed above. 90It will be further understood that may be within a range between and including any of the minimum and maximum values recited above.
[0027] According to yet another embodiment, the first filler precursor material may have a particular average particle size measured using laser diffraction spectroscopy. For example, the average particle size of the first filler precursor material may be about 10 micrometers or less, such as about 9 micrometers or less, or about 8 micrometers or less, or about 7 micrometers or less, or about 6 micrometers or less, or about 5 micrometers or less, or about 4 micrometers or less, or about 3 micrometers or less, or even about 3 micrometers or less. It will be understood that the average particle size of the first filler precursor material may be any value between and including any of the values recited above. It will be further understood that the average particle size of the first filler precursor material may be any value between and including any of the values recited above.
[0028] According to yet another embodiment, the first filler precursor material may be described as having a particular particle size distribution span (PSDS), the PSDS being (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler precursor material 90 D is equal to the particle size distribution measurement 10 is the D of the first filler precursor material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler precursor material 50It is equal to a particle size distribution measurement. For example, the PSDS of the first filler precursor material may be about 5 or less, such as about 4.5 or less, or about 4.0 or less, or about 3.5 or less, or about 3.0 or less, or even about 2.5 or less. It will be understood that the PSDS of the first filler precursor material may be any value between and including any of the values recited above. It will be further understood that the PSDS of the first filler precursor material may be any value between and including any of the values recited above.
[0029] According to yet another embodiment, the first filler precursor material can be described as having a particular average surface area as measured using Brunauer-Emmett-Teller (BET) surface area analysis (nitrogen adsorption). For example, the first filler precursor material can have an average surface area of about 8 m. 2 / g or less, for example, about 7.9m 2 / g or less, or about 7.5m 2 / g or less, or about 7.0m 2 / g or less, or about 6.5m 2 / g or less, or about 6.0m 2 / g or less, or about 5.5m 2 / g or less, or about 5.0m 2 / g or less, or about 4.5m 2 / g or less, or about 4.0m 2 / g or less, or even about 3.5m 2 According to yet another embodiment, the first filler precursor material may have an average surface area of at least about 1.2 m / g or less. 2 / g, e.g., at least about 2.2 m 2 / g. It will be understood that the average surface area of the first filler precursor material may be any value between and including any of the minimum values and any of the maximum values recited above. It will be further understood that the average surface area of the first filler precursor material may be within a range between and including any of the minimum values and any of the maximum values recited above.
[0030] According to other embodiments, the first filler precursor material may include a particular material. According to certain embodiments, the first filler precursor material may include a silica-based compound. According to yet other embodiments, the first filler precursor material may be comprised of a silica-based compound. According to other embodiments, the first filler precursor material may include silica. According to yet other embodiments, the first filler precursor material may be comprised of silica.
[0031] According to yet other embodiments, the forming mixture may include a particular content of the ceramic filler precursor component. For example, the content of the ceramic filler precursor component may be at least about 45% by volume, such as at least about 46% by volume, or at least about 47% by volume, or at least about 48% by volume, or at least about 49% by volume, or at least about 50% by volume, or at least about 51% by volume, or at least about 52% by volume, or at least about 53% by volume, or even at least about 54% by volume, based on the total volume of the forming mixture. According to yet other embodiments, the content of the ceramic filler precursor component may be about 57% by volume or less, such as about 56% by volume or less, or even about 55% by volume or less, based on the total volume of the forming mixture. It will be understood that the content of the ceramic filler precursor component may be any value between and including any of the minimum values and any of the maximum values listed above. It will be further understood that the content of the ceramic filler precursor component may be within a range between and including any of the minimum values and any of the maximum values listed above.
[0032] According to yet another embodiment, the ceramic filler precursor component may include a certain content of the first filler precursor material. For example, the content of the first filler precursor material may be at least about 80 vol.%, for example, at least about 81 vol.%, or at least about 82 vol.%, or at least about 83 vol.%, or at least about 84 vol.%, or at least about 85 vol.%, or at least about 86 vol.%, or at least about 87 vol.%, or at least about 88 vol.%, or at least about 89 vol.%, or even at least about 90 vol.%, based on the total volume of the ceramic filler precursor component. According to yet another embodiment, the content of the first filler precursor material may be about 100 vol.% or less, for example, about 99 vol.% or less, or about 98 vol.% or less, or about 97 vol.% or less, or about 96 vol.% or less, or about 95 vol.% or less, or about 94 vol.% or less, or about 93 vol.% or less, or even about 92 vol.% or less, based on the total volume of the ceramic filler precursor component. It will be understood that the content of the first filler precursor material may be any value between and including any of the minimum values and any of the maximum values recited above. It will be further understood that the content of the first filler precursor material may be within a range between and including any of the minimum values and any of the maximum values recited above.
[0033] According to yet other embodiments, the ceramic filler precursor composition may include a second filler precursor material.
[0034] According to yet another embodiment, the second filler precursor material may include a specific material. For example, the second filler precursor material may include a high dielectric constant ceramic material, such as a ceramic material having a dielectric constant of at least about 14. According to a specific embodiment, the second filler precursor material may include a high dielectric constant ceramic material, such as TiO2, SrTiO3, ZrTi2O6, MgTiO3, CaTiO3, BaTiO4, or any combination thereof.
[0035] According to yet another embodiment, the second filler precursor material may include TiO2 According to yet another embodiment, the second filler precursor material may consist of TiO2.
[0036] According to yet another embodiment, the ceramic filler precursor component may include a certain content of the second filler precursor material. For example, the content of the second filler precursor material may be at least about 1 vol.%, for example, at least about 2 vol.%, or at least about 3 vol.%, or at least about 4 vol.%, or at least about 5 vol.%, or at least about 6 vol.%, or at least about 7 vol.%, or at least about 8 vol.%, or at least about 9 vol.%, or even at least about 10 vol.%, based on the total volume of the ceramic filler precursor component. According to yet another embodiment, the content of the second filler precursor material may be about 20 vol.% or less, for example, about 19 vol.% or less, or about 18 vol.% or less, or about 17 vol.% or less, or about 16 vol.% or less, or about 15 vol.% or less, or about 14 vol.% or less, or about 13 vol.% or less, or about 12 vol.% or less, based on the total volume of the ceramic filler precursor component. It will be understood that the content of the second filler precursor material may be any value between and including any of the minimum values and any of the maximum values recited above. It will be further understood that the content of the second filler precursor material may be within a range between and including any of the minimum values and any of the maximum values recited above.
[0037] According to yet another embodiment, the ceramic filler precursor component may include a specific content of amorphous material. For example, the ceramic filler precursor component may include at least about 97%, such as at least about 98%, or even at least about 99% amorphous material. It will be understood that the content of amorphous material may be any value between and including any of the values recited above. It will be further understood that the content of amorphous material may be any value between and including any of the values recited above. According to another embodiment, the resin matrix precursor component may include a specific material. For example, the resin matrix precursor component may include a perfluoropolymer. According to yet another embodiment, the resin matrix precursor component may be composed of a perfluoropolymer.
[0038] According to yet another embodiment, the perfluoropolymer of the resin matrix precursor component can include a copolymer of tetrafluoroethylene (TFE), a copolymer of hexafluoropropylene (HFP), a terpolymer of tetrafluoroethylene (TFE), or any combination thereof. According to another embodiment, the perfluoropolymer of the resin matrix precursor component can include a copolymer of tetrafluoroethylene (TFE), a copolymer of hexafluoropropylene (HFP), a terpolymer of tetrafluoroethylene (TFE), or any combination thereof.
[0039] According to yet another embodiment, the perfluoropolymer of the resin matrix precursor component may comprise polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), or any combination thereof. According to yet another embodiment, the perfluoropolymer of the resin matrix precursor component may comprise polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), or any combination thereof.
[0040] According to yet other embodiments, the forming mixture may include a particular content of the resin matrix precursor component. For example, the content of the resin matrix precursor component may be at least about 45% by volume, such as at least about 46% by volume, or at least about 47% by volume, or at least about 48% by volume, or at least about 49% by volume, or at least about 50% by volume, or at least about 51% by volume, or at least about 52% by volume, or at least about 53% by volume, or at least about 54% by volume, or even at least about 55% by volume, based on the total volume of the forming mixture. According to still other embodiments, the content of the resin matrix precursor component is about 63% by volume or less, or about 62% by volume or less, or about 61% by volume or less, or about 60% by volume or less, or about 59% by volume or less, or about 58% by volume or less, or even about 57% by volume or less, based on the total volume of the forming mixture. It will be understood that the content of the resin matrix precursor component may be any value between and including any of the minimum values and any of the maximum values listed above. It will be further understood that the content of the resin matrix precursor component may be within a range between and including any of the minimum and maximum values recited above.
[0041] According to still other embodiments, the forming mixture may include a specific content of perfluoropolymer. For example, the content of perfluoropolymer may be at least about 45% by volume, for example, at least about 46% by volume, or at least about 47% by volume, or at least about 48% by volume, or at least about 49% by volume, or at least about 50% by volume, or at least about 51% by volume, or at least about 52% by volume, or at least about 53% by volume, or at least about 54% by volume, or even at least about 55% by volume, based on the total volume of the forming mixture. According to still other embodiments, the content of perfluoropolymer may be about 63% by volume or less, for example, about 62% by volume or less, or about 61% by volume or less, or about 60% by volume or less, or about 59% by volume or less, or about 58% by volume or less, or even about 57% by volume or less, based on the total volume of the forming mixture. It will be understood that the content of perfluoropolymer may be any value between and including any of the above minimum values and any of the above maximum values. It will be further understood that the perfluoropolymer content may be within a range between and including any of the minimum and maximum values recited above.
[0042] Turning now to embodiments of a dielectric substrate formed according to forming method 100, Figure 2 includes an illustration of a dielectric substrate 200. As shown in Figure 2, the dielectric substrate 200 may include a polymer-based core film 203 and a fluoropolymer-based adhesive layer 207. As further shown in Figure 2, the polymer-based core film 203 may include a resin matrix component 210 and a ceramic filler component 220.
[0043] According to certain embodiments, the ceramic filler component 220 may include a first filler material that may have certain properties that may improve the performance of the dielectric substrate 200 .
[0044] According to certain embodiments, the first filler material of the ceramic filler component 220 may have a particular size distribution. For purposes of the embodiments described herein, the particle size distribution of a material, e.g., the particle size distribution of a first filler material, is referred to as a particle size distribution D value, D 10 , D 50 and D. 90 Any combination of D from the particle size distribution can be used to describe the 10 The D value is defined as the particle size value below which 10% of the particles are smaller and above which 90% of the particles are larger. 50 The D value is defined as the particle size value below which 50% of the particles are smaller and above which 50% of the particles are larger. 90 A value is defined as the particle size value below which 90% of the particles are smaller and 10% of the particles are greater. For purposes of the embodiments described herein, particle size measurements for certain materials are performed using laser diffraction spectroscopy.
[0045] According to a particular embodiment, the first filler material of the ceramic filler component 220 has a particular size distribution D 10 For example, the D of the first filler material may have a value of 10 may be at least about 0.5 micrometers, e.g., at least about 0.6 micrometers, or at least about 0.7 micrometers, or at least about 0.8 micrometers, or at least about 0.9 micrometers, or at least about 1.0 micrometers, or at least about 1.1 micrometers, or even at least about 1.2 micrometers. According to yet other embodiments, the D of the first filler material 10 may be about 1.6 micrometers or less, such as about 1.5 micrometers or less, or even about 1.4 micrometers or less. 10 It will be understood that D may be any value between and including any of the minimum and maximum values listed above. 10It will be further understood that may be within a range between and including any of the minimum and maximum values recited above.
[0046] According to another embodiment, the first filler material of the ceramic filler component 220 has a particular size distribution D 50 For example, the D of the first filler material may have a value of 50 may be at least about 0.8 micrometers, e.g., at least about 0.9 micrometers, or at least about 1.0 micrometers, or at least about 1.1 micrometers, or at least about 1.2 micrometers, or at least about 1.3 micrometers, or at least about 1.4 micrometers, or at least about 1.5 micrometers, or at least about 1.6 micrometers, or at least about 1.7 micrometers, or at least about 1.8 micrometers, or at least about 1.9 micrometers, or at least about 2.0 micrometers, or at least about 2.1 micrometers, or even at least about 2.2 micrometers. According to yet other embodiments, the D of the first filler material 50 D of the first filler material may be about 2.7 micrometers or less, such as about 2.6 micrometers or less, or about 2.5 micrometers or less, or even about 2.4 micrometers or less. 50 It will be understood that D may be any value between and including any of the minimum and maximum values listed above. 50 It will be further understood that may be within a range between and including any of the minimum and maximum values recited above.
[0047] According to another embodiment, the first filler material of the ceramic filler component 220 has a particular size distribution D 90 For example, the D of the first filler material may have a value of 90may be at least about 1.5 micrometers, e.g., at least about 1.6 micrometers, or at least about 1.7 micrometers, or at least about 1.8 micrometers, or at least about 1.9 micrometers, or at least about 2.0 micrometers, or at least about 2.1 micrometers, or at least about 2.2 micrometers, or at least about 2.3 micrometers, or at least about 2.4 micrometers, or at least about 2.5 micrometers, or at least about 2.6 micrometers, or even at least about 2.7 micrometers. According to yet other embodiments, the D of the first filler material 90 may be about 8.0 micrometers or less, for example, about 7.5 micrometers or less, or about 7.0 micrometers or less, or about 6.5 micrometers or less, or about 6.0 micrometers or less, or about 5.5 micrometers or less, or about 5.4 micrometers or less, or about 5.3 micrometers or less, or about 5.2 micrometers or less, or even about 5.1 micrometers or less. 90 It will be understood that D may be any value between and including any of the minimum and maximum values listed above. 90 It will be further understood that may be within a range between and including any of the minimum and maximum values recited above.
[0048] According to yet other embodiments, the first filler material of the ceramic filler component 220 may have a particular average particle size as measured by laser diffraction spectroscopy. For example, the average particle size of the first filler material may be about 10 micrometers or less, such as about 9 micrometers or less, or about 8 micrometers or less, or about 7 micrometers or less, or about 6 micrometers or less, or about 5 micrometers or less, or about 4 micrometers or less, or about 3 micrometers or less, or even about 2 micrometers or less. It will be understood that the average particle size of the first filler material may be any value between and including any of the values recited above. It will be further understood that the average particle size of the first filler material may be any value between and including any of the values recited above.
[0049] According to yet another embodiment, the first filler material of the ceramic filler component 220 may be described as having a particular particle size distribution span (PSDS), the PSDS being (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler material 90 D is equal to the particle size distribution measurement 10 is the D of the first filler material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler material 50 It is equal to a particle size distribution measurement. For example, the PSDS of the first filler material may be about 5 or less, such as about 4.5 or less, or about 4.0 or less, or about 3.5 or less, or about 3.0 or less, or even about 2.5 or less. It will be understood that the PSDS of the first filler material may be any value between and including any of the values recited above. It will further be understood that the PSDS of the first filler material may be any value within a range between and including any of the values recited above.
[0050] According to yet another embodiment, the first filler material of the ceramic filler component 220 can be described as having a particular average surface area as measured using Brunauer-Emmett-Teller (BET) surface area analysis (nitrogen adsorption). For example, the first filler material can have an average surface area of about 8 m. 2 / g or less, for example, about 7.9m 2 / g or less, or about 7.5m 2 / g or less, or about 7.0m 2 / g or less, or about 6.5m 2 / g or less, or about 6.0m 2 / g or less, or about 5.5m 2 / g or less, or about 5.0m 2 / g or less, or about 4.5m 2 / g or less, or about 4.0m 2 / g or less, or even about 3.5m 2 According to yet another embodiment, the first filler material may have an average surface area of at least about 1.2 m / g or less. 2 / g, e.g., at least about 2.2 m 2 / g. It will be understood that the average surface area of the first filler material may be any value between and including any of the minimum values and any of the maximum values recited above. It will be further understood that the average surface area of the first filler material may be within a range between and including any of the minimum values and any of the maximum values recited above.
[0051] According to yet other embodiments, the fluoropolymer adhesive layer 207 may have a particular average thickness. For example, the average thickness of the adhesive layer 207 may be at least about 0.2 micrometers, such as at least about 0.5 micrometers, or at least about 1.0 micrometers, or at least about 1.5 micrometers, or at least about 2.0 micrometers, or at least about 2.5 micrometers, or even at least about 3.0 micrometers. According to yet other embodiments, the average thickness of adhesive layer 207 may be about 7 micrometers or less, such as about 6.5 or less, or about 6.0 or less, or about 5.5 or less, or about 5.0 or less, about 4.9 micrometers or less, or about 4.8 micrometers or less, about 4.7 micrometers or less, or about 4.6 micrometers or less, or about 4.5 micrometers or less, or about 4.4 micrometers or less, or about 4.3 micrometers or less, or about 4.2 micrometers or less, or about 4.1 micrometers or less, or about 4.1 micrometers or less, or about 4.0 micrometers or less, or about 3.9 micrometers or less, or about 3.8 micrometers or less, or about 3.7 micrometers or less, or about 3.6 micrometers or less, or even about 3.5 micrometers or less. It will be understood that the average thickness of adhesive layer 207 may be any value between and including any of the minimum values and any of the maximum values listed above. It will be further understood that the average thickness of adhesive layer 207 may be within a range between and including any of the minimum values and any of the maximum values recited above.
[0052] According to yet another embodiment, the fluoropolymer adhesive layer 207 may include a specific material. For example, the fluoropolymer adhesive layer 207 may include, but is not limited to, fluoropolymers (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene (mPTFE), copolymers and terpolymers of tetrafluoroethylene such as fluorinated ethylene-propylene (FEP), perfluoroalkoxy polymer resin (PFA), and modified perfluoroalkoxy polymer resin (mPFA), as well as derivatives and blends thereof. According to yet another embodiment, the fluoropolymer adhesive layer 207 may be composed of fluoropolymers (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene (mPTFE), copolymers and terpolymers of tetrafluoroethylene such as fluorinated ethylene-propylene (FEP), perfluoroalkoxy polymer resin (PFA), and modified perfluoroalkoxy polymer resin (mPFA), as well as derivatives and blends thereof.
[0053] According to other embodiments, the first filler material of the ceramic filler component 220 may include a particular material. According to certain embodiments, the first filler material may include a silica-based compound. According to yet other embodiments, the first filler material may be comprised of a silica-based compound. According to other embodiments, the first filler material may include silica. According to yet other embodiments, the first filler material may be comprised of silica.
[0054] According to yet other embodiments, the polymer-based core film 203 may include a particular content of the ceramic filler component 220. For example, the content of the ceramic filler component 220 may be at least about 45% by volume, such as at least about 46% by volume, or at least about 47% by volume, or at least about 48% by volume, or at least about 49% by volume, or at least about 50% by volume, or at least about 51% by volume, or at least about 52% by volume, or at least about 53% by volume, or even at least about 54% by volume, based on the total volume of the polymer-based core film 203. According to yet other embodiments, the content of the ceramic filler component 220 may be about 57% by volume or less, such as about 56% by volume or less, or even about 55% by volume or less, based on the total volume of the polymer-based core film 203. It will be understood that the content of the ceramic filler component 220 may be any value between and including any of the minimum values and any of the maximum values listed above. It will be further understood that the content of ceramic filler component 220 may be within a range between and including any of the minimum and maximum values recited above.
[0055] According to yet another embodiment, the dielectric substrate 200 may include a particular content of the ceramic filler component 220. For example, the content of the ceramic filler component 220 may be at least about 45% by volume, such as at least about 46% by volume, or at least about 47% by volume, or at least about 48% by volume, or at least about 49% by volume, or at least about 50% by volume, or at least about 51% by volume, or at least about 52% by volume, or at least about 53% by volume, or even at least about 54% by volume, based on the total volume of the dielectric substrate 200. According to yet another embodiment, the content of the ceramic filler component 220 may be about 57% by volume or less, such as about 56% by volume or less, or even about 55% by volume or less, based on the total volume of the dielectric substrate 200. It will be understood that the content of the ceramic filler component 220 may be any value between and including any of the minimum values and any of the maximum values listed above. It will be further understood that the content of ceramic filler component 220 may be within a range between and including any of the minimum and maximum values recited above.
[0056] According to yet other embodiments, the ceramic filler component 220 may include a particular content of the first filler material. For example, the content of the first filler material may be at least about 80 vol.%, such as at least about 81 vol.%, or at least about 82 vol.%, or at least about 83 vol.%, or at least about 84 vol.%, or at least about 85 vol.%, or at least about 86 vol.%, or at least about 87 vol.%, or at least about 88 vol.%, or at least about 89 vol.%, or even at least about 90 vol.%, based on the total volume of the ceramic filler component 220. According to yet other embodiments, the content of the first filler material may be about 100 vol.% or less, such as about 99 vol.% or less, or about 98 vol.% or less, or about 97 vol.% or less, or about 96 vol.% or less, or about 95 vol.% or less, or about 94 vol.% or less, or about 93 vol.% or less, or even about 92 vol.% or less, based on the total volume of the ceramic filler component 220. It will be appreciated that the content of the first filler material may be any value between and including any of the minimum values and any of the maximum values recited above. It will be further appreciated that the content of the first filler material may be within a range between and including any of the minimum values and any of the maximum values recited above.
[0057] According to yet other embodiments, the ceramic filler component 220 may include a second filler material.
[0058] According to yet other embodiments, the second filler material of the ceramic filler component 220 may include a particular material. For example, the second filler material may include a high dielectric constant ceramic material, such as a ceramic material having a dielectric constant of at least about 14. According to certain embodiments, the second filler material of the ceramic filler component 220 may include a high dielectric constant ceramic material, such as TiO2, SrTiO3, ZrTi2O6, MgTiO3, CaTiO3, BaTiO4, or any combination thereof.
[0059] According to yet another embodiment, the second filler material of the ceramic filler component 220 may include TiO2. According to yet another embodiment, the second filler material may be composed of TiO2.
[0060] According to yet other embodiments, the ceramic filler component 220 may include a certain content of the second filler material. For example, the content of the second filler material may be at least about 1 vol.%, such as at least about 2 vol.%, or at least about 3 vol.%, or at least about 4 vol.%, or at least about 5 vol.%, or at least about 6 vol.%, or at least about 7 vol.%, or at least about 8 vol.%, or at least about 9 vol.%, or even at least about 10 vol.%, based on the total volume of the ceramic filler component 220. According to yet other embodiments, the content of the second filler material may be about 20 vol.% or less, such as about 19 vol.% or less, or about 18 vol.% or less, or about 17 vol.% or less, or about 16 vol.% or less, or about 15 vol.% or less, or about 14 vol.% or less, or about 13 vol.% or less, or about 12 vol.% or less, based on the total volume of the ceramic filler component 220. It will be appreciated that the content of the second filler material may be any value between and including any of the minimum values and any of the maximum values recited above. It will be further appreciated that the content of the second filler material may be within a range between and including any of the minimum values and any of the maximum values recited above.
[0061] According to yet other embodiments, the ceramic filler component 220 may include a particular content of amorphous material. For example, the ceramic filler component 220 may include at least about 97%, such as at least about 98%, or even at least about 99% amorphous material. It will be understood that the content of amorphous material may be any value between and including any of the values recited above. It will be further understood that the content of amorphous material may be any value between and including any of the values recited above.
[0062] According to other embodiments, the resin matrix component 210 may include a particular material. For example, the resin matrix component 210 may include a perfluoropolymer. According to yet other embodiments, the resin matrix component 210 may be composed of a perfluoropolymer.
[0063] According to yet other embodiments, the perfluoropolymer of the resin matrix component 210 can include a copolymer of tetrafluoroethylene (TFE), a copolymer of hexafluoropropylene (HFP), a terpolymer of tetrafluoroethylene (TFE), or any combination thereof. According to other embodiments, the perfluoropolymer of the resin matrix component 210 can include a copolymer of tetrafluoroethylene (TFE), a copolymer of hexafluoropropylene (HFP), a terpolymer of tetrafluoroethylene (TFE), or any combination thereof.
[0064] According to yet other embodiments, the perfluoropolymer of the resin matrix component 210 may include polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), or any combination thereof. According to yet other embodiments, the perfluoropolymer of the resin matrix component 210 may consist of polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), or any combination thereof.
[0065] According to yet other embodiments, the polymer-based core film 203 may include a particular content of the resin matrix component 210. For example, the content of the resin matrix component 210 may be at least about 45 volume percent, such as at least about 46 volume percent, or at least about 47 volume percent, or at least about 48 volume percent, or at least about 49 volume percent, or at least about 50 volume percent, or at least about 51 volume percent, or at least about 52 volume percent, or at least about 53 volume percent, or at least about 54 volume percent, or even at least about 55 volume percent, based on the total volume of the polymer-based core film 203. According to yet other embodiments, the content of the resin matrix component 210 is about 63 volume percent or less, or about 62 volume percent or less, or about 61 volume percent or less, or about 60 volume percent or less, or about 59 volume percent or less, or about 58 volume percent or less, or even about 57 volume percent or less, based on the total volume of the polymer-based core film 203. It will be appreciated that the content of the resin matrix component 210 may be any value between and including any of the minimum values and any of the maximum values recited above. It will be further appreciated that the content of the resin matrix component 210 may be within a range between and including any of the minimum values and any of the maximum values recited above.
[0066] According to yet another embodiment, the dielectric substrate 200 may include a particular content of the resin matrix component 210. For example, the content of the resin matrix component 210 may be at least about 45% by volume, such as at least about 46% by volume, or at least about 47% by volume, or at least about 48% by volume, or at least about 49% by volume, or at least about 50% by volume, or at least about 51% by volume, or at least about 52% by volume, or at least about 53% by volume, or at least about 54% by volume, or even at least about 55% by volume, based on the total volume of the dielectric substrate 200. According to yet another embodiment, the content of the resin matrix component 210 is about 63% by volume or less, or about 62% by volume or less, or about 61% by volume or less, or about 60% by volume or less, or about 59% by volume or less, or about 58% by volume or less, or even about 57% by volume or less, based on the total volume of the dielectric substrate 200. It will be appreciated that the content of the resin matrix component 210 may be any value between and including any of the minimum values and any of the maximum values recited above. It will be further appreciated that the content of the resin matrix component 210 may be within a range between and including any of the minimum values and any of the maximum values recited above.
[0067] According to yet other embodiments, the polymer-based core film 203 may include a particular content of perfluoropolymer. For example, the content of perfluoropolymer may be at least about 45% by volume, such as at least about 46% by volume, or at least about 47% by volume, or at least about 48% by volume, or at least about 49% by volume, or at least about 50% by volume, or at least about 51% by volume, or at least about 52% by volume, or at least about 53% by volume, or at least about 54% by volume, or even at least about 55% by volume, based on the total volume of the polymer-based core film 203. According to yet other embodiments, the content of perfluoropolymer may be about 63% by volume or less, such as about 62% by volume or less, or about 61% by volume or less, or about 60% by volume or less, or about 59% by volume or less, or about 58% by volume or less, or even about 57% by volume or less, based on the total volume of the polymer-based core film 203. It will be understood that the content of perfluoropolymer may be any value between and including any of the minimum values and any of the maximum values listed above. It will be further understood that the perfluoropolymer content may be within a range between and including any of the minimum and maximum values recited above.
[0068] According to yet another embodiment, the dielectric substrate 200 may include a particular content of perfluoropolymer. For example, the content of perfluoropolymer may be at least about 45% by volume, for example, at least about 46% by volume, or at least about 47% by volume, or at least about 48% by volume, or at least about 49% by volume, or at least about 50% by volume, or at least about 51% by volume, or at least about 52% by volume, or at least about 53% by volume, or at least about 54% by volume, or even at least about 55% by volume, based on the total volume of the dielectric substrate 200. According to yet another embodiment, the content of perfluoropolymer may be about 63% by volume or less, for example, about 62% by volume or less, or about 61% by volume or less, or about 60% by volume or less, or about 59% by volume or less, or about 58% by volume or less, or even about 57% by volume or less, based on the total volume of the dielectric substrate 200. It will be understood that the content of perfluoropolymer may be any value between and including any of the minimum values and any of the maximum values listed above. It will be further understood that the perfluoropolymer content may be within a range between and including any of the minimum and maximum values recited above.
[0069] According to yet other embodiments, the polymer-based core film 203 may include a particular porosity measured using X-ray diffraction. For example, the porosity of the polymer-based core film 203 may be about 10% by volume or less, such as about 9% by volume or less, or about 8% by volume or less, or about 7% by volume or less, or about 6% by volume or less, or even about 5% by volume or less. It will be understood that the porosity of the dielectric polymer-based core film 203 may be any value between and including any of the values recited above. It will be further understood that the porosity of the polymer-based core film 203 may be any value between and including any of the values recited above.
[0070] According to yet other embodiments, the polymer-based core film 203 may have a particular average thickness. For example, the average thickness of the polymer-based core film 203 may be at least about 10 micrometers, such as at least about 15 micrometers, or at least about 20 micrometers, or at least about 25 micrometers, or at least about 30 micrometers, or at least about 35 micrometers, or at least about 40 micrometers, or at least about 45 micrometers, or at least about 50 micrometers, or at least about 55 micrometers, or at least about 60 micrometers, or at least about 65 micrometers, or at least about 70 micrometers, or even at least about 75 micrometers. According to yet other embodiments, the average thickness of the polymer-based core film 203 may be about 2000 micrometers or less, such as about 1800 micrometers or less, about 1600 micrometers or less, about 1400 micrometers or less, about 1200 micrometers or less, or about 1000 micrometers or less, or about 800 micrometers or less, or about 600 micrometers or less, or about 400 micrometers or less, or about 200 micrometers or less, or about 190 micrometers or less, or about 180 micrometers or less, or about 170 micrometers or less, or about 160 micrometers or less, or about 150 micrometers or less, or about 140 micrometers or less, or about 120 micrometers or less, or even about 100 micrometers or less. It will be understood that the average thickness of the polymer-based core film 203 may be any value between and including any of the minimum values and any of the maximum values listed above. It will be further understood that the average thickness of the polymeric core film 203 may be within a range between and including any of the minimum and maximum values set forth above.
[0071] According to yet another embodiment, the polymer-based core film 203 may have a particular dissipation factor (Df) measured in the range of 5 GHz at 20% RH. For example, the polymer-based core film 203 may have a dissipation factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the dissipation factor of the polymer-based core film 203 may be any value between and including any of the values recited above. It will be further understood that the dissipation factor of the polymer-based core film 203 may be any value between and including any of the values recited above.
[0072] According to yet another embodiment, the polymer-based core film 203 may have a particular loss factor (Df) measured in the range of 5 GHz at 80% RH. For example, the polymer-based core film 203 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the polymer-based core film 203 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the polymer-based core film 203 may be any value between and including any of the values recited above.
[0073] According to yet another embodiment, the polymer-based core film 203 may have a particular loss factor (Df) measured in the range of 10 GHz at 20% RH. For example, the polymer-based core film 203 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the polymer-based core film 203 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the polymer-based core film 203 may be any value between and including any of the values recited above.
[0074] According to yet another embodiment, the polymer-based core film 203 may have a particular loss factor (Df) measured in the range of 10 GHz at 80% RH. For example, the polymer-based core film 203 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the polymer-based core film 203 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the polymer-based core film 203 may be any value between and including any of the values recited above.
[0075] According to yet another embodiment, the polymer-based core film 203 may have a particular loss factor (Df) measured in the range of 28 GHz at 20% RH. For example, the polymer-based core film 203 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the polymer-based core film 203 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the polymer-based core film 203 may be any value between and including any of the values recited above.
[0076] According to yet another embodiment, the polymer-based core film 203 may have a particular loss factor (Df) measured in the range of 28 GHz at 80% RH. For example, the polymer-based core film 203 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the polymer-based core film 203 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the polymer-based core film 203 may be any value between and including any of the values recited above.
[0077] According to yet another embodiment, the polymer-based core film 203 may have a particular loss factor (Df) measured in the range of 39 GHz at 20% RH. For example, the polymer-based core film 203 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the polymer-based core film 203 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the polymer-based core film 203 may be any value between and including any of the values recited above.
[0078] According to yet another embodiment, the polymer-based core film 203 may have a particular loss factor (Df) measured in the range of 39 GHz at 80% RH. For example, the polymer-based core film 203 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the polymer-based core film 203 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the polymer-based core film 203 may be any value between and including any of the values recited above.
[0079] According to yet another embodiment, the polymer-based core film 203 may have a particular loss factor (Df) measured in the range of 76-81 GHz at 20% RH. For example, the polymer-based core film 203 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the polymer-based core film 203 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the polymer-based core film 203 may be any value between and including any of the values recited above.
[0080] According to yet another embodiment, the polymer-based core film 203 may have a particular loss factor (Df) measured in the range of 76-81 GHz at 80% RH. For example, the polymer-based core film 203 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the polymer-based core film 203 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the polymer-based core film 203 may be any value between and including any of the values recited above.
[0081] According to yet another embodiment, the polymer-based core film 203 may have a particular coefficient of thermal expansion, measured according to IPC-TM-650 2.4.24 Rev. C Glass Transition Temperature and Z-Axis Thermal Expansion by TMA. For example, the polymer-based core film 203 may have a coefficient of thermal expansion of about 80 ppm / ° C. or less.
[0082] It will be understood that any dielectric substrate described herein (e.g., polymer-based core film 203) may include additional polymer-based layers on the outer surface of the initially described dielectric substrate, and that the additional polymer-based layers may include a filler as described herein (i.e., may be a filled polymer layer) or may not include a filler (i.e., an unfilled polymer layer).
[0083] According to yet other embodiments, the dielectric substrate 200 may have a particular average thickness. For example, the average thickness of the dielectric substrate 200 may be at least about 10 micrometers, such as at least about 15 micrometers, or at least about 20 micrometers, or at least about 25 micrometers, or at least about 30 micrometers, or at least about 35 micrometers, or at least about 40 micrometers, or at least about 45 micrometers, or at least about 50 micrometers, or at least about 55 micrometers, or at least about 60 micrometers, or at least about 65 micrometers, or at least about 70 micrometers, or even at least about 75 micrometers. According to yet other embodiments, the average thickness of the dielectric substrate 200 may be about 2000 micrometers or less, for example, about 1800 micrometers or less, about 1600 micrometers or less, about 1400 micrometers or less, about 1200 micrometers or less, or about 1000 micrometers or less, or about 800 micrometers or less, or about 600 micrometers or less, or about 400 micrometers or less, or about 200 micrometers or less, or about 190 micrometers or less, or about 180 micrometers or less, or about 170 micrometers or less, or about 160 micrometers or less, or about 150 micrometers or less, or about 140 micrometers or less, or about 120 micrometers or less, or even about 100 micrometers or less. It will be understood that the average thickness of the dielectric substrate 200 may be any value between and including any of the minimum values and any of the maximum values listed above. It will be further understood that the average thickness of the dielectric substrate 200 may be within a range between and including any of the minimum values and any of the maximum values listed above.
[0084] According to yet another embodiment, the dielectric substrate 200 may have a particular loss factor (Df) measured in the range of 5 GHz at 20% RH. For example, the dielectric substrate 200 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the dielectric substrate 200 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the dielectric substrate 200 may be any value between and including any of the values recited above.
[0085] According to yet another embodiment, the dielectric substrate 200 may have a particular loss factor (Df) measured in the range of 5 GHz at 80% RH. For example, the dielectric substrate 200 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the dielectric substrate 200 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the dielectric substrate 200 may be any value between and including any of the values recited above.
[0086] According to yet another embodiment, the dielectric substrate 200 may have a particular loss factor (Df) measured in the range of 10 GHz at 20% RH. For example, the dielectric substrate 200 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the dielectric substrate 200 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the dielectric substrate 200 may be any value between and including any of the values recited above.
[0087] According to yet another embodiment, the dielectric substrate 200 may have a particular loss factor (Df) measured in the range of 10 GHz at 80% RH. For example, the dielectric substrate 200 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the dielectric substrate 200 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the dielectric substrate 200 may be any value between and including any of the values recited above.
[0088] According to yet another embodiment, the dielectric substrate 200 may have a particular loss factor (Df) measured in the range of 28 GHz at 20% RH. For example, the dielectric substrate 200 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the dielectric substrate 200 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the dielectric substrate 200 may be any value between and including any of the values recited above.
[0089] According to yet another embodiment, the dielectric substrate 200 may have a particular loss factor (Df) measured in the range of 28 GHz at 80% RH. For example, the dielectric substrate 200 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the dielectric substrate 200 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the dielectric substrate 200 may be any value between and including any of the values recited above.
[0090] According to yet another embodiment, the dielectric substrate 200 may have a particular loss factor (Df) measured in the range of 39 GHz at 20% RH. For example, the dielectric substrate 200 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the dielectric substrate 200 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the dielectric substrate 200 may be any value between and including any of the values recited above.
[0091] According to yet another embodiment, the dielectric substrate 200 may have a particular loss factor (Df) measured in the range of 39 GHz at 80% RH. For example, the dielectric substrate 200 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the dielectric substrate 200 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the dielectric substrate 200 may be any value between and including any of the values recited above.
[0092] According to yet another embodiment, the dielectric substrate 200 may have a particular loss factor (Df) measured in the range of 76-81 GHz at 20% RH. For example, the dielectric substrate 200 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the dielectric substrate 200 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the dielectric substrate 200 may be any value between and including any of the values recited above.
[0093] According to yet another embodiment, the dielectric substrate 200 may have a particular loss factor (Df) measured in the range of 76-81 GHz at 80% RH. For example, the dielectric substrate 200 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the dielectric substrate 200 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the dielectric substrate 200 may be any value between and including any of the values recited above.
[0094] According to yet another embodiment, the dielectric substrate 200 may have a particular coefficient of thermal expansion, measured according to IPC-TM-650 2.4.24 Rev. C Glass Transition Temperature and Z-Axis Thermal Expansion by TMA, For example, the dielectric substrate 200 may have a coefficient of thermal expansion of about 80 ppm / ° C. or less.
[0095] It will be understood that any dielectric substrate described herein (e.g., dielectric substrate 200) may include additional polymer-based layers on an outer surface of the initially described dielectric substrate, and that the additional polymer-based layers may include a filler as described herein (i.e., may be a filled polymer layer) or may not include a filler (i.e., an unfilled polymer layer).
[0096] Reference is now made to embodiments of copper clad laminates that may include the dielectric substrate described herein. Such additional embodiments described herein generally relate to copper clad laminates that may include a copper foil layer and a dielectric substrate overlying the copper foil layer. According to certain embodiments, the dielectric substrate may include a polymer-based core film and a fluoropolymer-based adhesive layer. According to certain embodiments, the polymer-based core film may include a resin matrix component and a ceramic filler component.
[0097] Turning now to a method of forming a copper clad laminate, Figure 3 includes a diagram illustrating a forming method 300 for forming a copper clad laminate according to embodiments described herein. According to certain embodiments, the forming method 300 can include a first step 310 of providing a copper foil layer, a second step 320 of combining a resin matrix precursor component and a ceramic filler precursor component to form a forming mixture, a third step 330 of forming the forming mixture into a polymer-based core film, and a fourth step 340 of coating the polymer-based core film with a fluoropolymer-based adhesive layer to form a copper clad laminate.
[0098] According to certain embodiments, the ceramic filler precursor composition may include a first filler precursor material that may have particular properties that may improve the performance of the dielectric substrate formed by the forming method 300.
[0099] According to certain embodiments, the first filler precursor material may have a particular size distribution. For purposes of the embodiments described herein, the particle size distribution of a material, e.g., the particle size distribution of a first filler precursor material, is referred to as the particle size distribution D value, D 10 , D 50 and D. 90 Any combination of D from the particle size distribution can be used to describe the 10 The D value is defined as the particle size value below which 10% of the particles are smaller and above which 90% of the particles are larger. 50 The D value is defined as the particle size value below which 50% of the particles are smaller and above which 50% of the particles are larger. 90 A value is defined as the particle size value below which 90% of the particles are smaller and 10% of the particles are greater. For purposes of the embodiments described herein, particle size measurements for certain materials are performed using laser diffraction spectroscopy.
[0100] According to a particular embodiment, the first filler precursor material has a particular size distribution D 10 For example, the D of the first filler precursor material may have a value of 10 may be at least about 0.5 micrometers, e.g., at least about 0.6 micrometers, or at least about 0.7 micrometers, or at least about 0.8 micrometers, or at least about 0.9 micrometers, or at least about 1.0 micrometers, or at least about 1.1 micrometers, or even at least about 1.2 micrometers. According to yet other embodiments, the D of the first filler material 10 may be about 1.6 micrometers or less, such as about 1.5 micrometers or less, or even about 1.4 micrometers or less. 10 It will be understood that D may be any value between and including any of the minimum and maximum values listed above. 10 It will be further understood that may be within a range between and including any of the minimum and maximum values recited above.
[0101] According to another embodiment, the first filler precursor material has a particular size distribution D 50 For example, the D of the first filler precursor material may have a value of 50 may be at least about 0.8 micrometers, e.g., at least about 0.9 micrometers, or at least about 1.0 micrometers, or at least about 1.1 micrometers, or at least about 1.2 micrometers, or at least about 1.3 micrometers, or at least about 1.4 micrometers, or at least about 1.5 micrometers, or at least about 1.6 micrometers, or at least about 1.7 micrometers, or at least about 1.8 micrometers, or at least about 1.9 micrometers, or at least about 2.0 micrometers, or at least about 2.1 micrometers, or even at least about 2.2 micrometers. According to yet other embodiments, the D of the first filler material 50 D of the first filler precursor material may be about 2.7 micrometers or less, such as about 2.6 micrometers or less, or about 2.5 micrometers or less, or even about 2.4 micrometers or less. 50 It will be understood that D may be any value between and including any of the minimum and maximum values listed above. 50 It will be further understood that may be within a range between and including any of the minimum and maximum values recited above.
[0102] According to another embodiment, the first filler precursor material has a particular size distribution D 90 For example, the D of the first filler precursor material may have a value of 90may be at least about 1.5 micrometers, e.g., at least about 1.6 micrometers, or at least about 1.7 micrometers, or at least about 1.8 micrometers, or at least about 1.9 micrometers, or at least about 2.0 micrometers, or at least about 2.1 micrometers, or at least about 2.2 micrometers, or at least about 2.3 micrometers, or at least about 2.2 micrometers, or at least about 2.5 micrometers, or at least about 2.6 micrometers, or even at least about 2.7 micrometers. According to yet other embodiments, the D of the first filler material 90 may be about 8.0 micrometers or less, for example, about 7.5 micrometers or less, or about 7.0 micrometers or less, or about 6.5 micrometers or less, or about 6.0 micrometers or less, or about 5.5 micrometers or less, or about 5.4 micrometers or less, or about 5.3 micrometers or less, or about 5.2 micrometers or less, or even about 5.1 micrometers or less. 90 It will be understood that D may be any value between and including any of the minimum and maximum values listed above. 90 It will be further understood that may be within a range between and including any of the minimum and maximum values recited above.
[0103] According to yet another embodiment, the first filler precursor material may have a particular average particle size measured using laser diffraction spectroscopy. For example, the average particle size of the first filler precursor material may be about 10 micrometers or less, such as about 9 micrometers or less, or about 8 micrometers or less, or about 7 micrometers or less, or about 6 micrometers or less, or about 5 micrometers or less, or about 4 micrometers or less, or about 3 micrometers or less, or even about 2 micrometers or less. It will be understood that the average particle size of the first filler precursor material may be any value between and including any of the values recited above. It will be further understood that the average particle size of the first filler precursor material may be any value between and including any of the values recited above.
[0104] According to yet another embodiment, the first filler precursor material may be described as having a particular particle size distribution span (PSDS), the PSDS being (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler precursor material 90 D is equal to the particle size distribution measurement 10 is the D of the first filler precursor material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler precursor material 50 It is equal to a particle size distribution measurement. For example, the PSDS of the first filler precursor material may be about 5 or less, such as about 4.5 or less, or about 4.0 or less, or about 3.5 or less, or about 3.0 or less, or even about 2.5 or less. It will be understood that the PSDS of the first filler precursor material may be any value between and including any of the values recited above. It will be further understood that the PSDS of the first filler precursor material may be any value between and including any of the values recited above.
[0105] According to yet another embodiment, the first filler precursor material can be described as having a particular average surface area as measured using Brunauer-Emmett-Teller (BET) surface area analysis (nitrogen adsorption). For example, the first filler precursor material can have an average surface area of about 8 m. 2 / g or less, for example, about 7.9m 2 / g or less, or about 7.5m 2 / g or less, or about 7.0m 2 / g or less, or about 6.5m 2 / g or less, or about 6.0m 2 / g or less, or about 5.5m 2 / g or less, or about 5.0m 2 / g or less, or about 4.5m 2 / g or less, or about 4.0m 2 / g or less, or even about 3.5m 2 According to yet another embodiment, the first filler precursor material may have an average surface area of at least about 1.2 m / g or less. 2 / g, e.g., at least about 2.2 m 2 / g. It will be understood that the average surface area of the first filler precursor material may be any value between and including any of the minimum values and any of the maximum values recited above. It will be further understood that the average surface area of the first filler precursor material may be within a range between and including any of the minimum values and any of the maximum values recited above.
[0106] According to other embodiments, the first filler precursor material may include a particular material. According to certain embodiments, the first filler precursor material may include a silica-based compound. According to yet other embodiments, the first filler precursor material may be comprised of a silica-based compound. According to other embodiments, the first filler precursor material may include silica. According to yet other embodiments, the first filler precursor material may be comprised of silica.
[0107] According to yet other embodiments, the forming mixture may include a particular content of the ceramic filler precursor component. For example, the content of the ceramic filler precursor component may be at least about 45% by volume, such as at least about 46% by volume, or at least about 47% by volume, or at least about 48% by volume, or at least about 49% by volume, or at least about 50% by volume, or at least about 51% by volume, or at least about 52% by volume, or at least about 53% by volume, or even at least about 54% by volume, based on the total volume of the forming mixture. According to yet other embodiments, the content of the ceramic filler precursor component may be about 57% by volume or less, such as about 56% by volume or less, or even about 55% by volume or less, based on the total volume of the forming mixture. It will be understood that the content of the ceramic filler precursor component may be any value between and including any of the minimum values and any of the maximum values listed above. It will be further understood that the content of the ceramic filler precursor component may be within a range between and including any of the minimum values and any of the maximum values listed above.
[0108] According to yet another embodiment, the ceramic filler precursor component may include a certain content of the first filler precursor material. For example, the content of the first filler precursor material may be at least about 80 vol.%, for example, at least about 81 vol.%, or at least about 82 vol.%, or at least about 83 vol.%, or at least about 84 vol.%, or at least about 85 vol.%, or at least about 86 vol.%, or at least about 87 vol.%, or at least about 88 vol.%, or at least about 89 vol.%, or even at least about 90 vol.%, based on the total volume of the ceramic filler precursor component. According to yet another embodiment, the content of the first filler precursor material may be about 100 vol.% or less, for example, about 99 vol.% or less, or about 98 vol.% or less, or about 97 vol.% or less, or about 96 vol.% or less, or about 95 vol.% or less, or about 94 vol.% or less, or about 93 vol.% or less, or even about 92 vol.% or less, based on the total volume of the ceramic filler precursor component. It will be understood that the content of the first filler precursor material may be any value between and including any of the minimum values and any of the maximum values recited above. It will be further understood that the content of the first filler precursor material may be within a range between and including any of the minimum values and any of the maximum values recited above.
[0109] According to yet other embodiments, the ceramic filler precursor composition may include a second filler precursor material.
[0110] According to yet another embodiment, the second filler precursor material may include a specific material. For example, the second filler precursor material may include a high dielectric constant ceramic material, such as a ceramic material having a dielectric constant of at least about 14. According to a specific embodiment, the second filler precursor material may include a high dielectric constant ceramic material, such as TiO2, SrTiO3, ZrTi2O6, MgTiO3, CaTiO3, BaTiO4, or any combination thereof.
[0111] According to yet another embodiment, the second filler precursor material may include TiO2 According to yet another embodiment, the second filler precursor material may consist of TiO2.
[0112] According to yet another embodiment, the ceramic filler precursor component may include a certain content of the second filler precursor material. For example, the content of the second filler precursor material may be at least about 1 vol.%, for example, at least about 2 vol.%, or at least about 3 vol.%, or at least about 4 vol.%, or at least about 5 vol.%, or at least about 6 vol.%, or at least about 7 vol.%, or at least about 8 vol.%, or at least about 9 vol.%, or even at least about 10 vol.%, based on the total volume of the ceramic filler precursor component. According to yet another embodiment, the content of the second filler precursor material may be about 20 vol.% or less, for example, about 19 vol.% or less, or about 18 vol.% or less, or about 17 vol.% or less, or about 16 vol.% or less, or about 15 vol.% or less, or about 14 vol.% or less, or about 13 vol.% or less, or about 12 vol.% or less, based on the total volume of the ceramic filler precursor component. It will be understood that the content of the second filler precursor material may be any value between and including any of the minimum values and any of the maximum values recited above. It will be further understood that the content of the second filler precursor material may be within a range between and including any of the minimum values and any of the maximum values recited above.
[0113] According to yet other embodiments, the ceramic filler precursor component may include a particular content of amorphous material. For example, the ceramic filler precursor component may include at least about 97%, such as at least about 98%, or even at least about 99% amorphous material. It will be understood that the content of amorphous material may be any value between and including any of the values recited above. It will be further understood that the content of amorphous material may be any value between and including any of the values recited above.
[0114] Turning now to an embodiment of a copper clad laminate formed according to forming method 300, Figure 4 includes an illustration of a copper clad laminate 400. As shown in Figure 4, copper clad laminate 400 may include a copper foil layer 402 and a dielectric substrate 405 overlying a surface of copper foil layer 402. As further shown in Figure 4, dielectric substrate 405 may include a polymer-based core film 403 and a fluoropolymer-based adhesive layer 407. As further shown in Figure 4, polymer-based core film 403 may include a resin matrix component 410 and a ceramic filler component 420.
[0115] According to certain embodiments, the ceramic filler component 420 may include a first filler material that may have certain properties that may improve the performance of the copper clad laminate 400 .
[0116] According to certain embodiments, the first filler material of the ceramic filler component 420 may have a particular size distribution. For purposes of the embodiments described herein, the particle size distribution of a material, e.g., the particle size distribution of a first filler material, is referred to as a particle size distribution D value, D 10 , D 50 and D. 90 Any combination of D from the particle size distribution can be used to describe the 10 The D value is defined as the particle size value below which 10% of the particles are smaller and above which 90% of the particles are larger. 50 The D value is defined as the particle size value below which 50% of the particles are smaller and above which 50% of the particles are larger. 90 A value is defined as the particle size value below which 90% of the particles are smaller and 10% of the particles are greater. For purposes of the embodiments described herein, particle size measurements for certain materials are performed using laser diffraction spectroscopy.
[0117] According to a particular embodiment, the first filler material of the ceramic filler component 420 has a particular size distribution D 10 For example, the D of the first filler material may have a value of 10may be at least about 0.5 micrometers, e.g., at least about 0.6 micrometers, or at least about 0.7 micrometers, or at least about 0.8 micrometers, or at least about 0.9 micrometers, or at least about 1.0 micrometers, or at least about 1.1 micrometers, or even at least about 1.2 micrometers. According to yet other embodiments, the D of the first filler material 10 may be about 1.6 micrometers or less, such as about 1.5 micrometers or less, or even about 1.4 micrometers or less. 10 It will be understood that D may be any value between and including any of the minimum and maximum values listed above. 10 It will be further understood that may be within a range between and including any of the minimum and maximum values recited above.
[0118] According to another embodiment, the first filler material of the ceramic filler component 420 has a particular size distribution D 50 For example, the D of the first filler material may have a value of 50 may be at least about 0.8 micrometers, e.g., at least about 0.9 micrometers, or at least about 1.0 micrometers, or at least about 1.1 micrometers, or at least about 1.2 micrometers, or at least about 1.3 micrometers, or at least about 1.4 micrometers, or at least about 1.5 micrometers, or at least about 1.6 micrometers, or at least about 1.7 micrometers, or at least about 1.8 micrometers, or at least about 1.9 micrometers, or at least about 2.0 micrometers, or at least about 2.1 micrometers, or even at least about 2.2 micrometers. According to yet other embodiments, the D of the first filler material 50D of the first filler material may be about 2.7 micrometers or less, such as about 2.6 micrometers or less, or about 2.5 micrometers or less, or even about 2.4 micrometers or less. 50 It will be understood that D may be any value between and including any of the minimum and maximum values listed above. 50 It will be further understood that may be within a range between and including any of the minimum and maximum values recited above.
[0119] According to another embodiment, the first filler material of the ceramic filler component 420 has a particular size distribution D 90 For example, the D of the first filler material may have a value of 90 may be at least about 1.5 micrometers, e.g., at least about 1.6 micrometers, or at least about 1.7 micrometers, or at least about 1.8 micrometers, or at least about 1.9 micrometers, or at least about 2.0 micrometers, or at least about 2.1 micrometers, or at least about 2.2 micrometers, or at least about 2.3 micrometers, or at least about 2.2 micrometers, or at least about 2.5 micrometers, or at least about 2.6 micrometers, or even at least about 2.7 micrometers. According to yet other embodiments, the D of the first filler material 90 may be about 8.0 micrometers or less, for example, about 7.5 micrometers or less, or about 7.0 micrometers or less, or about 6.5 micrometers or less, or about 6.0 micrometers or less, or about 5.5 micrometers or less, or about 5.4 micrometers or less, or about 5.3 micrometers or less, or about 5.2 micrometers or less, or even about 5.1 micrometers or less. 90 It will be understood that D may be any value between and including any of the minimum and maximum values listed above. 90It will be further understood that may be within a range between and including any of the minimum and maximum values recited above.
[0120] According to yet other embodiments, the first filler material of the ceramic filler component 420 may have a particular average particle size as measured by laser diffraction spectroscopy. For example, the average particle size of the first filler material may be about 10 micrometers or less, such as about 9 micrometers or less, or about 8 micrometers or less, or about 7 micrometers or less, or about 6 micrometers or less, or about 5 micrometers or less, or about 4 micrometers or less, or about 3 micrometers or less, or even about 2 micrometers or less. It will be understood that the average particle size of the first filler material may be any value between and including any of the values recited above. It will be further understood that the average particle size of the first filler material may be any value between and including any of the values recited above.
[0121] According to yet another embodiment, the first filler material of the ceramic filler component 420 may be described as having a particular particle size distribution span (PSDS), the PSDS being (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler material 90 D is equal to the particle size distribution measurement 10 is the D of the first filler material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler material 50 It is equal to a particle size distribution measurement. For example, the PSDS of the first filler material may be about 5 or less, such as about 4.5 or less, or about 4.0 or less, or about 3.5 or less, or about 3.0 or less, or even about 2.5 or less. It will be understood that the PSDS of the first filler material may be any value between and including any of the values recited above. It will further be understood that the PSDS of the first filler material may be any value within a range between and including any of the values recited above.
[0122] According to yet another embodiment, the first filler material of the ceramic filler component 420 can be described as having a particular average surface area as measured using Brunauer-Emmett-Teller (BET) surface area analysis (nitrogen adsorption). For example, the first filler material can have an average surface area of about 8 m. 2 / g or less, for example, about 7.9m 2 / g or less, or about 7.5m 2 / g or less, or about 7.0m 2 / g or less, or about 6.5m 2 / g or less, or about 6.0m 2 / g or less, or about 5.5m 2 / g or less, or about 5.0m 2 / g or less, or about 4.5m 2 / g or less, or about 4.0m 2 / g or less, or even about 3.5m 2 According to yet another embodiment, the first filler material may have an average surface area of at least about 1.2 m / g or less. 2 / g, e.g., at least about 2.2 m 2 / g. It will be understood that the average surface area of the first filler material may be any value between and including any of the minimum values and any of the maximum values recited above. It will be further understood that the average surface area of the first filler material may be within a range between and including any of the minimum values and any of the maximum values recited above.
[0123] According to yet other embodiments, the fluoropolymer adhesive layer 407 can have a particular average thickness. For example, the average thickness of the adhesive layer 407 can be at least about 0.2 micrometers, such as at least about 0.5 micrometers, or at least about 1.0 micrometers, or at least about 1.5 micrometers, or at least about 2.0 micrometers, or at least about 2.5 micrometers, or even at least about 3.0 micrometers. According to yet other embodiments, the average thickness of adhesive layer 407 may be about 7 micrometers or less, such as about 6.5 or less, or about 6.0 or less, or about 5.0 or less, about 4.9 micrometers or less, or about 4.8 micrometers or less, or about 4.7 micrometers or less, or about 4.6 micrometers or less, or about 4.5 micrometers or less, or about 4.4 micrometers or less, or about 4.3 micrometers or less, or about 4.2 micrometers or less, or about 4.1 micrometers or less, or about 4.1 micrometers or less, or about 4.0 micrometers or less, or about 3.9 micrometers or less, or about 3.8 micrometers or less, or about 3.7 micrometers or less, or about 3.6 micrometers or less, or even about 3.5 micrometers or less. It will be understood that the average thickness of adhesive layer 407 may be any value between and including any of the minimum values and any of the maximum values listed above. It will be further understood that the average thickness of adhesive layer 407 may be within a range between and including any of the minimum values and any of the maximum values recited above.
[0124] According to yet another embodiment, the fluoropolymer adhesive layer 407 may include a specific material. For example, the fluoropolymer adhesive layer 207 may include, but is not limited to, fluoropolymers (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene (mPTFE), copolymers and terpolymers of tetrafluoroethylene such as fluorinated ethylene-propylene (FEP), perfluoroalkoxy polymer resins (PFA), and modified perfluoroalkoxy polymer resins (mPFA), and derivatives and blends thereof. According to yet another embodiment, the fluoropolymer adhesive layer 407 may be composed of fluoropolymers (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene (mPTFE), copolymers and terpolymers of tetrafluoroethylene such as fluorinated ethylene-propylene (FEP), perfluoroalkoxy polymer resins (PFA), and modified perfluoroalkoxy polymer resins (mPFA), and derivatives and blends thereof.
[0125] According to other embodiments, the first filler material of the ceramic filler component 420 may include a particular material. According to certain embodiments, the first filler material may include a silica-based compound. According to yet other embodiments, the first filler material may be comprised of a silica-based compound. According to other embodiments, the first filler material may include silica. According to yet other embodiments, the first filler material may be comprised of silica.
[0126] According to yet other embodiments, the polymer-based core film 403 may include a particular content of the ceramic filler component 420. For example, the content of the ceramic filler component 420 may be at least about 45% by volume, such as at least about 46% by volume, or at least about 47% by volume, or at least about 48% by volume, or at least about 49% by volume, or at least about 50% by volume, or at least about 51% by volume, or at least about 52% by volume, or at least about 53% by volume, or even at least about 54% by volume, based on the total volume of the polymer-based core film 203. According to yet other embodiments, the content of the ceramic filler component 420 may be about 57% by volume or less, such as about 56% by volume or less, or even about 55% by volume or less, based on the total volume of the polymer-based core film 203. It will be understood that the content of the ceramic filler component 420 may be any value between and including any of the minimum values and any of the maximum values listed above. It will be further understood that the content of ceramic filler component 420 may be within a range between and including any of the minimum and maximum values recited above.
[0127] According to yet other embodiments, the dielectric substrate 405 may include a particular content of the ceramic filler component 420. For example, the content of the ceramic filler component 420 may be at least about 45% by volume, such as at least about 46% by volume, or at least about 47% by volume, or at least about 48% by volume, or at least about 49% by volume, or at least about 50% by volume, or at least about 51% by volume, or at least about 52% by volume, or at least about 53% by volume, or even at least about 54% by volume, based on the total volume of the dielectric substrate 405. According to yet other embodiments, the content of the ceramic filler component 420 may be about 57% by volume or less, such as about 56% by volume or less, or even about 55% by volume or less, based on the total volume of the dielectric substrate 400. It will be understood that the content of the ceramic filler component 420 may be any value between and including any of the minimum values and any of the maximum values listed above. It will be further understood that the content of ceramic filler component 420 may be within a range between and including any of the minimum and maximum values recited above.
[0128] According to yet other embodiments, the ceramic filler component 420 may include a certain content of the first filler material. For example, the content of the first filler material may be at least about 80 vol.%, such as at least about 81 vol.%, or at least about 82 vol.%, or at least about 83 vol.%, or at least about 84 vol.%, or at least about 85 vol.%, or at least about 86 vol.%, or at least about 87 vol.%, or at least about 88 vol.%, or at least about 89 vol.%, or even at least about 90 vol.%, based on the total volume of the ceramic filler component 420. According to yet other embodiments, the content of the first filler material may be about 100 vol.% or less, such as about 99 vol.% or less, or about 98 vol.% or less, or about 97 vol.% or less, or about 96 vol.% or less, or about 95 vol.% or less, or about 94 vol.% or less, or about 93 vol.% or less, or even about 92 vol.% or less, based on the total volume of the ceramic filler component 220. It will be appreciated that the content of the first filler material may be any value between and including any of the minimum values and any of the maximum values recited above. It will be further appreciated that the content of the first filler material may be within a range between and including any of the minimum values and any of the maximum values recited above.
[0129] According to yet other embodiments, the ceramic filler component 420 may include a second filler material.
[0130] According to yet other embodiments, the second filler material of the ceramic filler component 420 may include a particular material. For example, the second filler material may include a high dielectric constant ceramic material, such as a ceramic material having a dielectric constant of at least about 14. According to certain embodiments, the second filler material of the ceramic filler component 420 may include a high dielectric constant ceramic material, such as TiO2, SrTiO3, ZrTi2O6, MgTiO3, CaTiO3, BaTiO4, or any combination thereof.
[0131] According to yet another embodiment, the second filler material of the ceramic filler component 420 may include TiO2. According to yet another embodiment, the second filler material may be composed of TiO2.
[0132] According to yet another embodiment, the ceramic filler component 420 may include a certain content of the second filler material. For example, the content of the second filler material may be at least about 1 vol.%, such as at least about 2 vol.%, or at least about 3 vol.%, or at least about 4 vol.%, or at least about 5 vol.%, or at least about 6 vol.%, or at least about 7 vol.%, or at least about 8 vol.%, or at least about 9 vol.%, or even at least about 10 vol.%, based on the total volume of the ceramic filler component 420. According to yet another embodiment, the content of the second filler material may be about 20 vol.% or less, such as about 19 vol.% or less, or about 18 vol.% or less, or about 17 vol.% or less, or about 16 vol.% or less, or about 15 vol.% or less, or about 14 vol.% or less, or about 13 vol.% or less, or about 12 vol.% or less, based on the total volume of the ceramic filler component 220. It will be appreciated that the content of the second filler material may be any value between and including any of the minimum values and any of the maximum values recited above. It will be further appreciated that the content of the second filler material may be within a range between and including any of the minimum values and any of the maximum values recited above.
[0133] According to yet other embodiments, the ceramic filler component 420 may include a particular content of amorphous material. For example, the ceramic filler component 420 may include at least about 97%, such as at least about 98%, or even at least about 99% amorphous material. It will be understood that the content of amorphous material may be any value between and including any of the values recited above. It will be further understood that the content of amorphous material may be any value between and including any of the values recited above.
[0134] According to other embodiments, the resin matrix component 410 may include a particular material. For example, the resin matrix component 410 may include a perfluoropolymer. According to yet other embodiments, the resin matrix component 410 may be composed of a perfluoropolymer.
[0135] According to yet other embodiments, the perfluoropolymer of the resin matrix component 410 can include a copolymer of tetrafluoroethylene (TFE), a copolymer of hexafluoropropylene (HFP), a terpolymer of tetrafluoroethylene (TFE), or any combination thereof. According to other embodiments, the perfluoropolymer of the resin matrix component 410 can be comprised of a copolymer of tetrafluoroethylene (TFE), a copolymer of hexafluoropropylene (HFP), a terpolymer of tetrafluoroethylene (TFE), or any combination thereof.
[0136] According to yet other embodiments, the perfluoropolymer of the resin matrix component 410 may comprise polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), or any combination thereof. According to yet other embodiments, the perfluoropolymer of the resin matrix component 410 may be comprised of polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), or any combination thereof.
[0137] According to yet another embodiment, the polymer-based core film 403 may include a certain content of the resin matrix component 410. For example, the content of the resin matrix component 410 may be at least about 45 volume %, such as at least about 46 volume %, or at least about 47 volume %, or at least about 48 volume %, or at least about 49 volume %, or at least about 50 volume %, or at least about 51 volume %, or at least about 52 volume %, or at least about 53 volume %, or at least about 54 volume %, or even at least about 55 volume %, based on the total volume of the dielectric substrate 400. According to yet another embodiment, the content of the resin matrix component 410 is about 63 volume % or less, or about 62 volume % or less, or about 61 volume % or less, or about 60 volume % or less, or about 59 volume % or less, or about 58 volume % or less, or even about 57 volume % or less, based on the total volume of the polymer-based core film 403. It will be appreciated that the content of the resin matrix component 410 may be any value between and including any of the minimum values and any of the maximum values recited above. It will be further appreciated that the content of the resin matrix component 410 may be within a range between and including any of the minimum values and any of the maximum values recited above.
[0138] According to yet another embodiment, the dielectric substrate 400 may include a particular content of the resin matrix component 410. For example, the content of the resin matrix component 410 may be at least about 45% by volume, such as at least about 46% by volume, or at least about 47% by volume, or at least about 48% by volume, or at least about 49% by volume, or at least about 50% by volume, or at least about 51% by volume, or at least about 52% by volume, or at least about 53% by volume, or at least about 54% by volume, or even at least about 55% by volume, based on the total volume of the dielectric substrate 400. According to yet another embodiment, the content of the resin matrix component 410 is about 63% by volume or less, or about 62% by volume or less, or about 61% by volume or less, or about 60% by volume or less, or about 59% by volume or less, or about 58% by volume or less, or even about 57% by volume or less, based on the total volume of the dielectric substrate 400. It will be appreciated that the content of the resin matrix component 410 may be any value between and including any of the minimum values and any of the maximum values recited above. It will be further appreciated that the content of the resin matrix component 410 may be within a range between and including any of the minimum values and any of the maximum values recited above.
[0139] According to yet another embodiment, the polymer-based core film 403 may include a particular content of perfluoropolymer. For example, the content of perfluoropolymer may be at least about 45% by volume, such as at least about 46% by volume, or at least about 47% by volume, or at least about 48% by volume, or at least about 49% by volume, or at least about 50% by volume, or at least about 51% by volume, or at least about 52% by volume, or at least about 53% by volume, or at least about 54% by volume, or even at least about 55% by volume, based on the total volume of the dielectric substrate 405. According to yet another embodiment, the content of perfluoropolymer may be about 63% by volume or less, such as about 62% by volume or less, or about 61% by volume or less, or about 60% by volume or less, or about 59% by volume or less, or about 58% by volume or less, or even about 57% by volume or less, based on the total volume of the polymer-based core film 403. It will be understood that the content of perfluoropolymer may be any value between and including any of the minimum values and any of the maximum values listed above. It will be further understood that the perfluoropolymer content may be within a range between and including any of the minimum and maximum values recited above.
[0140] According to yet another embodiment, the dielectric substrate 405 may include a particular content of perfluoropolymer. For example, the content of perfluoropolymer may be at least about 45% by volume, for example, at least about 46% by volume, or at least about 47% by volume, or at least about 48% by volume, or at least about 49% by volume, or at least about 50% by volume, or at least about 51% by volume, or at least about 52% by volume, or at least about 53% by volume, or at least about 54% by volume, or even at least about 55% by volume, based on the total volume of the dielectric substrate 405. According to yet another embodiment, the content of perfluoropolymer may be about 63% by volume or less, for example, about 62% by volume or less, or about 61% by volume or less, or about 60% by volume or less, or about 59% by volume or less, or about 58% by volume or less, or even about 57% by volume or less, based on the total volume of the dielectric substrate 200. It will be understood that the content of perfluoropolymer may be any value between and including any of the minimum values and any of the maximum values listed above. It will be further understood that the perfluoropolymer content may be within a range between and including any of the minimum and maximum values recited above.
[0141] According to yet other embodiments, the polymer-based core film 403 may include a particular porosity measured using X-ray diffraction. For example, the porosity of the substrate 405 may be about 10 vol. % or less, such as about 9 vol. % or less, or about 8 vol. % or less, or about 7 vol. % or less, or about 6 vol. % or less, or even about 5 vol. % or less. It will be understood that the porosity of the polymer-based core film 403 may be any value between and including any of the values recited above. It will be further understood that the porosity of the polymer-based core film 403 may be any value between and including any of the values recited above.
[0142] According to yet other embodiments, the polymer-based core film 403 may have a particular average thickness. For example, the average thickness of the polymer-based core film 403 may be at least about 10 micrometers, such as at least about 15 micrometers, or at least about 20 micrometers, or at least about 25 micrometers, or at least about 30 micrometers, or at least about 35 micrometers, or at least about 40 micrometers, or at least about 45 micrometers, or at least about 50 micrometers, or at least about 55 micrometers, or at least about 60 micrometers, or at least about 65 micrometers, or at least about 70 micrometers, or even at least about 75 micrometers. According to yet other embodiments, the average thickness of the polymer-based core film 403 may be about 2000 micrometers or less, such as about 1800 micrometers or less, about 1600 micrometers or less, about 1400 micrometers or less, about 1200 micrometers or less, or about 1000 micrometers or less, or about 800 micrometers or less, or about 600 micrometers or less, or about 400 micrometers or less, or about 200 micrometers or less, or about 190 micrometers or less, or about 180 micrometers or less, or about 170 micrometers or less, or about 160 micrometers or less, or about 150 micrometers or less, or about 140 micrometers or less, or about 120 micrometers or less, or even about 100 micrometers or less. It will be understood that the average thickness of the polymer-based core film 403 may be any value between and including any of the minimum values and any of the maximum values listed above. It will be further understood that the average thickness of the polymeric core film 403 may be within a range between and including any of the minimum and maximum values set forth above.
[0143] According to yet another embodiment, the polymer-based core film 403 may have a particular loss factor (Df) measured in the range of 5 GHz at 20% RH. For example, the polymer-based core film 403 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the polymer-based core film 403 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the polymer-based core film 403 may be any value between and including any of the values recited above.
[0144] According to yet another embodiment, the polymer-based core film 403 may have a particular loss factor (Df) measured in the range of 5 GHz at 80% RH. For example, the polymer-based core film 403 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the polymer-based core film 403 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the polymer-based core film 403 may be any value between and including any of the values recited above.
[0145] According to yet another embodiment, the polymer-based core film 403 may have a particular loss factor (Df) measured in the range of 10 GHz at 20% RH. For example, the polymer-based core film 403 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the polymer-based core film 403 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the polymer-based core film 403 may be any value between and including any of the values recited above.
[0146] According to yet another embodiment, the polymer-based core film 403 may have a particular loss factor (Df) measured in the range of 10 GHz at 80% RH. For example, the polymer-based core film 403 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the polymer-based core film 403 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the polymer-based core film 403 may be any value between and including any of the values recited above.
[0147] According to yet another embodiment, the polymer-based core film 403 may have a particular loss factor (Df) measured in the range of 28 GHz at 20% RH. For example, the polymer-based core film 403 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the polymer-based core film 403 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the polymer-based core film 403 may be any value between and including any of the values recited above.
[0148] According to yet another embodiment, the polymer-based core film 403 may have a particular loss factor (Df) measured in the range of 28 GHz at 80% RH. For example, the polymer-based core film 403 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the polymer-based core film 403 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the polymer-based core film 403 may be any value between and including any of the values recited above.
[0149] According to yet another embodiment, the polymer-based core film 403 may have a particular loss factor (Df) measured in the range of 39 GHz at 20% RH. For example, the polymer-based core film 403 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the polymer-based core film 403 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the polymer-based core film 403 may be any value between and including any of the values recited above.
[0150] According to yet another embodiment, the polymer-based core film 403 may have a particular loss factor (Df) measured in the range of 39 GHz at 80% RH. For example, the polymer-based core film 403 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the polymer-based core film 403 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the polymer-based core film 403 may be any value between and including any of the values recited above.
[0151] According to yet another embodiment, the polymer-based core film 403 may have a particular loss factor (Df) measured in the range of 76-81 GHz at 20% RH. For example, the polymer-based core film 403 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the polymer-based core film 403 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the polymer-based core film 403 may be any value between and including any of the values recited above.
[0152] According to yet another embodiment, the polymer-based core film 403 may have a particular loss factor (Df) measured in the range of 76-81 GHz at 80% RH. For example, the polymer-based core film 403 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the polymer-based core film 403 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the polymer-based core film 403 may be any value between and including any of the values recited above.
[0153] According to yet another embodiment, the polymer-based core film 403 may have a particular coefficient of thermal expansion, measured according to IPC-TM-650 2.4.24 Rev. C Glass Transition Temperature and Z-Axis Thermal Expansion by TMA. For example, the polymer-based core film 403 may have a coefficient of thermal expansion of about 80 ppm / ° C. or less.
[0154] According to yet other embodiments, the dielectric substrate 405 may have a particular porosity measured using X-ray diffraction. For example, the porosity of the substrate 405 may be about 10% by volume or less, such as about 9% by volume or less, or about 8% by volume or less, or about 7% by volume or less, or about 6% by volume or less, or even about 5% by volume or less. It will be appreciated that the porosity of the dielectric substrate 405 may be any value between and including any of the values recited above. It will be further appreciated that the porosity of the dielectric substrate 405 may be any value between and including any of the values recited above.
[0155] According to yet other embodiments, the dielectric substrate 405 may have a particular average thickness. For example, the average thickness of the dielectric substrate 405 may be at least about 10 micrometers, such as at least about 15 micrometers, or at least about 20 micrometers, or at least about 25 micrometers, or at least about 30 micrometers, or at least about 35 micrometers, or at least about 40 micrometers, or at least about 45 micrometers, or at least about 50 micrometers, or at least about 55 micrometers, or at least about 60 micrometers, or at least about 65 micrometers, or at least about 70 micrometers, or even at least about 75 micrometers. According to yet other embodiments, the average thickness of the dielectric substrate 405 may be about 2000 micrometers or less, for example, about 1800 micrometers or less, about 1600 micrometers or less, about 1400 micrometers or less, about 1200 micrometers or less, or about 1000 micrometers or less, or about 800 micrometers or less, or about 600 micrometers or less, or about 400 micrometers or less, or about 200 micrometers or less, or about 190 micrometers or less, or about 180 micrometers or less, or about 170 micrometers or less, or about 160 micrometers or less, or about 150 micrometers or less, or about 140 micrometers or less, or about 120 micrometers or less, or even about 100 micrometers or less. It will be understood that the average thickness of the dielectric substrate 405 may be any value between and including any of the minimum values and any of the maximum values listed above. It will be further understood that the average thickness of the dielectric substrate 405 may be within a range between and including any of the minimum values and any of the maximum values listed above.
[0156] According to yet another embodiment, the dielectric substrate 405 may have a particular loss factor (Df) measured in the range of 5 GHz at 20% RH. For example, the dielectric substrate 405 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the dielectric substrate 405 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the dielectric substrate 405 may be any value between and including any of the values recited above.
[0157] According to yet another embodiment, the dielectric substrate 405 may have a particular loss factor (Df) measured in the range of 5 GHz at 80% RH. For example, the dielectric substrate 405 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the dielectric substrate 405 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the dielectric substrate 405 may be any value between and including any of the values recited above.
[0158] According to yet another embodiment, the dielectric substrate 405 may have a particular loss factor (Df) measured in the range of 10 GHz at 20% RH. For example, the dielectric substrate 405 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the dielectric substrate 405 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the dielectric substrate 405 may be any value between and including any of the values recited above.
[0159] According to yet another embodiment, the dielectric substrate 405 may have a particular loss factor (Df) measured in the range of 10 GHz at 80% RH. For example, the dielectric substrate 405 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the dielectric substrate 405 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the dielectric substrate 405 may be any value between and including any of the values recited above.
[0160] According to yet another embodiment, the dielectric substrate 405 may have a particular loss factor (Df) measured in the range of 28 GHz at 20% RH. For example, the dielectric substrate 405 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the dielectric substrate 405 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the dielectric substrate 405 may be any value between and including any of the values recited above.
[0161] According to yet another embodiment, the dielectric substrate 405 may have a particular loss factor (Df) measured in the range of 28 GHz at 80% RH. For example, the dielectric substrate 405 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the dielectric substrate 405 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the dielectric substrate 405 may be any value between and including any of the values recited above.
[0162] According to yet another embodiment, the dielectric substrate 405 may have a particular loss factor (Df) measured in the range of 39 GHz at 20% RH. For example, the dielectric substrate 405 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the dielectric substrate 405 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the dielectric substrate 405 may be any value between and including any of the values recited above.
[0163] According to yet another embodiment, the dielectric substrate 405 may have a particular loss factor (Df) measured in the range of 39 GHz at 80% RH. For example, the dielectric substrate 405 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the dielectric substrate 405 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the dielectric substrate 405 may be any value between and including any of the values recited above.
[0164] According to yet another embodiment, the dielectric substrate 405 may have a particular loss factor (Df) measured in the range of 76-81 GHz at 20% RH. For example, the dielectric substrate 405 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the dielectric substrate 405 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the dielectric substrate 405 may be any value between and including any of the values recited above.
[0165] According to yet another embodiment, the dielectric substrate 405 may have a particular loss factor (Df) measured in the range of 76-81 GHz at 80% RH. For example, the dielectric substrate 405 may have a loss factor of about 0.005 or less, such as about 0.004 or less, or about 0.003 or less, or about 0.002 or less, or about 0.0019 or less, or about 0.0018 or less, or about 0.0017 or less, or about 0.0016 or less, or about 0.0015 or less, or about 0.0014 or less. It will be understood that the loss factor of the dielectric substrate 405 may be any value between and including any of the values recited above. It will be further understood that the loss factor of the dielectric substrate 405 may be any value between and including any of the values recited above.
[0166] According to yet another embodiment, the dielectric substrate 405 may have a particular coefficient of thermal expansion, measured according to IPC-TM-650 2.4.24 Rev. C Glass Transition Temperature and Z-Axis Thermal Expansion by TMA, For example, the dielectric substrate 405 may have a coefficient of thermal expansion of about 80 ppm / ° C. or less.
[0167] It will be understood that any copper clad laminate described herein may include an additional polymer-based layer on the outer surface of the first described dielectric substrate, between the substrate and any copper foil layers of the copper clad laminate. Also as noted herein, the additional polymer-based layer may include a filler as described herein (i.e., may be a filled polymer layer) or may not include a filler (i.e., may be an unfilled polymer layer).
[0168] Turning now to a method of forming a printed circuit board, Figure 5 includes a diagram illustrating a forming method 500 for forming a printed circuit board according to embodiments described herein. According to certain embodiments, the forming method 500 can include a first step 510 of providing a copper foil layer, a second step 520 of combining a resin matrix precursor component and a ceramic filler precursor component to form a forming mixture, a third step 530 of forming the forming mixture into a polymer-based core film, a fourth step 540 of coating the polymer-based core film with a fluoropolymer-based adhesive layer to form a copper clad laminate, and a fourth step 550 of forming the copper clad laminate into a printed circuit board.
[0169] It will be understood that all descriptions, details, and features provided herein with reference to formation method 100 and / or formation method 300 may also apply to or describe corresponding aspects of formation method 500.
[0170] Turning now to embodiments of printed circuit boards formed according to forming method 500, Figure 6 includes an illustration of a printed circuit board 600. As shown in Figure 6, the printed circuit board 600 may include a copper clad laminate 601, which may include a copper foil layer 602 and a dielectric substrate 605 overlying a surface of the copper foil layer 402. As further shown in Figure 6, the dielectric substrate 605 may include a polymer-based core film 603 and a fluoropolymer-based adhesive layer 607. As further shown in Figure 6, the polymer-based core film 603 may include a resin matrix component 610 and a ceramic filler component 620.
[0171] Again, it will be understood that all descriptions provided herein with respect to dielectric substrate 200 (405) and / or copper clad laminate 400 are further applicable to modified versions of printed circuit board 600, including all components of printed circuit board 600.
[0172] Many different aspects and embodiments are possible. Some of these aspects and embodiments are described herein. After reading this specification, a person skilled in the art will understand that these aspects and embodiments are merely exemplary and do not limit the scope of the present invention. The embodiment can be according to any one or more of the embodiments listed below.
[0173] Embodiment 1. A dielectric substrate comprising a polymer-based core film and a fluoropolymer-based adhesive layer, the polymer-based core film comprising a resin matrix component and a ceramic filler component, the ceramic filler component comprising a first filler material, the first filler material having a particle size distribution of at least about 0.5 micrometers and no greater than about 1.6 micrometers D 10 , D of at least about 0.8 micrometers and not more than about 2.7 micrometers 50 and D of at least about 1.5 micrometers and not more than about 4.7 micrometers 90 A dielectric substrate comprising:
[0174] Embodiment 2. A dielectric substrate comprising a polymer-based core film and a fluoropolymer-based adhesive layer, the polymer-based core film comprising a resin matrix component and a ceramic filler component, the ceramic filler component comprising a first filler material, the first filler material further comprising an average particle size of about 10 micrometers or less and a particle size distribution span (PSDS) of about 5 or less, the PSDS being less than or equal to (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler material 90 D is equal to the particle size distribution measurement 10 is the D of the first filler material10 D is equal to the particle size distribution measurement 50 is the D of the first filler material 50 Dielectric substrate, equal to grain size distribution measurements.
[0175] Embodiment 3. A dielectric substrate comprising a polymer-based core film and a fluoropolymer-based adhesive layer, the polymer-based core film comprising a resin matrix component and a ceramic filler component, the ceramic filler component comprising a first filler material, the first filler material having an average particle size of about 10 micrometers or less and an average particle size of about 8 micrometers or less. 2 The dielectric substrate further comprises an average surface area of less than or equal to 1 / g.
[0176] Embodiment 4. The particle size distribution of the first filler material is at least about 0.5 micrometers and no greater than about 1.6 micrometers D 10 4. The dielectric substrate of embodiment 2 or 3, comprising:
[0177] Embodiment 5. The particle size distribution of the first filler material is at least about 0.8 micrometers and no greater than about 2.7 micrometers D 50 4. The dielectric substrate of embodiment 2 or 3, comprising:
[0178] Embodiment 6. The particle size distribution of the first filler material is at least about 1.5 micrometers and no greater than about 4.7 micrometers D 90 4. The dielectric substrate of embodiment 2 or 3, comprising:
[0179] Embodiment 7. The dielectric substrate of embodiment 1, wherein the first filler material further comprises an average particle size of about 10 micrometers or less.
[0180] Embodiment 8. A dielectric substrate as described in any one of embodiments 2, 3, and 7, wherein the first filler material comprises an average particle size of about 10 micrometers or less, or about 9 micrometers or less, or about 8 micrometers or less, or about 7 micrometers or less, or about 6 micrometers or less, or about 5 micrometers or less, or about 4 micrometers or less, or about 3 micrometers or less, or about 2 micrometers or less.
[0181] Embodiment 9. The first filler material comprises a particle size distribution span (PSDS) of about 5 or less, the PSDS being (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler material 90 D is equal to the particle size distribution measurement 10 is the D of the first filler material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler material 50 4. The dielectric substrate of embodiment 1 or 3, wherein the particle size distribution measurement is equal to the particle size distribution measurement.
[0182] Embodiment 10. The first filler material is about 8m 2 3. The dielectric substrate of embodiment 1 or 2, further comprising an average surface area of less than or equal to 1 / g.
[0183] Embodiment 11. A dielectric substrate according to any one of embodiments 1, 2, and 3, wherein the fluoropolymer adhesive layer has an average thickness of at least about 0.2 micrometers.
[0184] Embodiment 12. A dielectric substrate according to any one of embodiments 1, 2, and 3, wherein the fluoropolymer adhesive layer has an average thickness of about 7 micrometers or less.
[0185] Embodiment 13. The dielectric substrate of any one of embodiments 1, 2, and 3, wherein the fluoropolymer-based adhesive layer comprises a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene (mPTFE), copolymers and terpolymers of tetrafluoroethylene such as fluorinated ethylene-propylene (FEP), perfluoroalkoxy polymer resins (PFA), and modified perfluoroalkoxy polymer resins (mPFA), and derivatives and blends thereof. According to yet other embodiments, the fluoropolymer-based adhesive layer 207 may be composed of a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene.
[0186] Embodiment 14. The dielectric substrate according to any one of embodiments 1, 2, and 3, wherein the fluoropolymer-based adhesive layer is composed of a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene (mPTFE), copolymers and terpolymers of tetrafluoroethylene such as fluorinated ethylene-propylene (FEP), perfluoroalkoxy polymer resins (PFA), and modified perfluoroalkoxy polymer resins (mPFA), and derivatives and blends thereof. According to yet another embodiment, the fluoropolymer-based adhesive layer 207 may be composed of a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene.
[0187] Embodiment 15. A dielectric substrate according to any one of embodiments 1, 2 and 3, wherein the fluoropolymer adhesive layer is a PFA layer.
[0188] Embodiment 16. A dielectric substrate according to any one of embodiments 1, 2, and 3, wherein the first filler material comprises a silica-based compound.
[0189] Embodiment 17. A dielectric substrate according to any one of embodiments 1, 2, and 3, wherein the first filler material comprises silica.
[0190] Embodiment 18. A dielectric substrate according to any one of embodiments 1, 2, and 3, wherein the resin matrix comprises a perfluoropolymer.
[0191] Embodiment 19. The dielectric substrate of embodiment 18, wherein the perfluoropolymer comprises a copolymer of tetrafluoroethylene (TFE), a copolymer of hexafluoropropylene (HFP), a terpolymer of tetrafluoroethylene (TFE), or any combination thereof.
[0192] Embodiment 20. The dielectric substrate of embodiment 18, wherein the perfluoropolymer comprises polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), or any combination thereof.
[0193] Embodiment 21. The dielectric substrate of embodiment 18, wherein the perfluoropolymer is comprised of polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), or any combination thereof.
[0194] Embodiment 22. A dielectric substrate according to any one of embodiments 1, 2, and 3, wherein the content of the resin matrix component is at least about 45 volume % based on the total volume of the polymer-based core film.
[0195] Embodiment 23. A dielectric substrate according to any one of embodiments 1, 2, and 3, wherein the content of the resin matrix component is about 63 volume % or less, based on the total volume of the polymer-based core film.
[0196] Embodiment 24. The dielectric substrate of embodiment 18, wherein the perfluoropolymer content is at least about 45% by volume, based on the total volume of the polymer-based core film.
[0197] Embodiment 25. A dielectric substrate as described in embodiment 18, wherein the perfluoropolymer content is about 63 volume % or less, based on the total volume of the polymer-based core film.
[0198] Embodiment 26. A dielectric substrate according to any one of embodiments 1, 2, and 3, wherein the content of the ceramic filler component is at least about 45 volume percent, based on the total volume of the polymer-based core film.
[0199] Embodiment 27. A dielectric substrate according to any one of embodiments 1, 2, and 3, wherein the content of the ceramic filler component is about 57 volume % or less, based on the total volume of the polymer-based core film.
[0200] Embodiment 28. A dielectric substrate according to any one of embodiments 1, 2, and 3, wherein the content of the first filler material is at least about 80 volume % based on the total volume of the ceramic filler component.
[0201] Embodiment 29. A dielectric substrate according to any one of embodiments 1, 2, and 3, wherein the content of the first filler material is about 100% by volume or less, based on the total volume of the ceramic filler component.
[0202] Embodiment 30. A dielectric substrate according to any one of embodiments 1, 2, and 3, wherein the ceramic filler component further comprises a second filler material.
[0203] Embodiment 31. The dielectric substrate of embodiment 30, wherein the second filler material comprises a high dielectric constant ceramic material.
[0204] Embodiment 32. The dielectric substrate of embodiment 31, wherein the high dielectric constant ceramic material has a dielectric constant of at least about 14.
[0205] Embodiment 33. The dielectric substrate of embodiment 31, wherein the ceramic filler component further comprises TiO2, SrTiO3, ZrTi2O6, MgTiO3, CaTiO3, BaTiO4, or any combination thereof.
[0206] Embodiment 34. The dielectric substrate of embodiment 30, wherein the content of the second filler material is at least about 1 volume percent, based on the total volume of the ceramic filler component.
[0207] Embodiment 35. The dielectric substrate of embodiment 30, wherein the content of the second filler material is about 20 volume % or less, based on the total volume of the ceramic filler component.
[0208] Embodiment 36. The dielectric substrate of any one of embodiments 1, 2, and 3, wherein the ceramic filler component is at least about 97% amorphous.
[0209] Embodiment 37. A dielectric substrate according to any one of embodiments 1, 2, and 3, wherein the polymer-based core film comprises no more than about 10% by volume porosity.
[0210] Embodiment 38. A dielectric substrate according to any one of embodiments 1, 2, and 3, wherein the polymer-based core film comprises an average thickness of at least about 10 micrometers.
[0211] Embodiment 39. A dielectric substrate according to any one of embodiments 1, 2, and 3, wherein the polymer-based core film comprises an average thickness of about 2000 micrometers or less.
[0212] Embodiment 40. A dielectric substrate according to any one of embodiments 1, 2, and 3, wherein the dielectric substrate comprises a loss factor (5 GHz, 20% RH) of about 0.005 or less.
[0213] Embodiment 41. A dielectric substrate according to any one of embodiments 1, 2, and 3, wherein the dielectric substrate comprises a loss factor (5 GHz, 20% RH) of about 0.0014 or less.
[0214] Embodiment 42. A dielectric substrate according to any one of embodiments 1, 2, and 3, wherein the dielectric substrate comprises a coefficient of thermal expansion (all axes) of about 80 ppm / °C or less.
[0215] Embodiment 43. A dielectric substrate according to any one of embodiments 1, 2, and 3, wherein the dielectric substrate comprises moisture absorption of about 0.05% or less.
[0216] Embodiment 44. A copper clad laminate comprising a copper foil layer and a dielectric substrate covering the copper foil layer, the dielectric substrate comprising a polymer-based core film and a fluoropolymer-based adhesive layer, the polymer-based core film comprising a resin matrix component and a ceramic filler component, the ceramic filler component comprising a first filler material, the particle size distribution of the first filler material being at least about 0.5 micrometers and no greater than about 1.6 micrometers D 10 , D of at least about 0.8 micrometers and not more than about 2.7 micrometers 50 and D of at least about 1.5 micrometers and not more than about 4.7 micrometers 90 4. A copper clad laminate comprising:
[0217] Embodiment 45. A copper clad laminate comprising a copper foil layer and a dielectric substrate covering the copper foil layer, the dielectric substrate comprising a polymer-based core film and a fluoropolymer-based adhesive layer, the polymer-based core film comprising a resin matrix component and a ceramic filler component, the ceramic filler component comprising a first filler material, the first filler material further comprising an average particle size of about 10 micrometers or less and a particle size distribution span (PSDS) of about 5 or less, the PSDS being less than (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler material 90 D is equal to the particle size distribution measurement 10 is the D of the first filler material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler material 50 Copper clad laminate, equal to particle size distribution measurements.
[0218] Embodiment 46. A copper clad laminate comprising a copper foil layer and a dielectric substrate covering the copper foil layer, the dielectric substrate comprising a polymer-based core film and a fluoropolymer-based adhesive layer, the polymer-based core film comprising a resin matrix component and a ceramic filler component, the ceramic filler component comprising a first filler material, the first filler material comprising an average particle size of about 10 micrometers or less and a ceramic filler size of about 8 micrometers or less. 2 / g or less.
[0219] Embodiment 47. The particle size distribution of the first filler material is at least about 0.5 micrometers and no greater than about 1.6 micrometers D 10 47. The copper clad laminate of embodiment 45 or 46, comprising:
[0220] Embodiment 48. The particle size distribution of the first filler material is at least about 0.8 micrometers and no greater than about 2.7 micrometers D 50 47. The copper clad laminate of embodiment 45 or 46, comprising:
[0221] Embodiment 49. The particle size distribution of the first filler material is at least about 1.5 micrometers and no greater than about 4.7 micrometers D 90 47. The copper clad laminate of embodiment 45 or 46, comprising:
[0222] Embodiment 50. The copper clad laminate of embodiment 44, wherein the first filler material further comprises an average particle size of about 10 micrometers or less.
[0223] Embodiment 51. The copper clad laminate of any one of embodiments 44, 45, and 46, wherein the first filler material comprises an average particle size of about 10 micrometers or less.
[0224] Embodiment 52. The first filler material comprises a particle size distribution span (PSDS) of about 5 or less, the PSDS being (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler material 90 D is equal to the particle size distribution measurement10 is the D of the first filler material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler material 50 47. The copper clad laminate of embodiment 44 or 46, wherein the particle size distribution measurement is equal to the particle size distribution measurement.
[0225] Embodiment 53. The first filler material is about 8 m 2 46. The copper clad laminate of embodiment 44 or 45, further comprising an average surface area of less than or equal to 1 / g.
[0226] Embodiment 54. A copper clad laminate according to any one of embodiments 44, 45, and 46, wherein the fluoropolymer adhesive layer has an average thickness of at least about 0.2 micrometers.
[0227] Embodiment 55. A copper clad laminate according to any one of embodiments 44, 45, and 46, wherein the fluoropolymer adhesive layer has an average thickness of about 7 micrometers or less.
[0228] Embodiment 56. The copper clad laminate according to any one of embodiments 44, 45, and 46, wherein the fluoropolymer-based adhesive layer comprises a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene (mPTFE), copolymers and terpolymers of tetrafluoroethylene such as fluorinated ethylene-propylene (FEP), perfluoroalkoxy polymer resins (PFA), and modified perfluoroalkoxy polymer resins (mPFA), as well as derivatives and blends thereof. According to yet another embodiment, the fluoropolymer-based adhesive layer 207 may be composed of a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene.
[0229] Embodiment 57. The copper clad laminate according to any one of embodiments 44, 45, and 46, wherein the fluoropolymer-based adhesive layer is made of a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene (mPTFE), copolymers and terpolymers of tetrafluoroethylene such as fluorinated ethylene-propylene (FEP), perfluoroalkoxy polymer resins (PFA), and modified perfluoroalkoxy polymer resins (mPFA), and derivatives and blends thereof. According to yet another embodiment, the fluoropolymer-based adhesive layer 207 may be made of a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene.
[0230] Embodiment 58. A copper clad laminate according to any one of embodiments 44, 45, and 46, wherein the fluoropolymer adhesive layer is a PFA layer.
[0231] Embodiment 59. The copper clad laminate of any one of embodiments 44, 45, and 46, wherein the first filler material comprises a silica-based compound.
[0232] Embodiment 60. The copper clad laminate of any one of embodiments 44, 45, and 46, wherein the first filler material comprises silica.
[0233] Embodiment 61. A copper clad laminate according to any one of embodiments 44, 45, and 46, wherein the resin matrix comprises a perfluoropolymer.
[0234] Embodiment 62. The copper clad laminate of embodiment 61, wherein the perfluoropolymer comprises a copolymer of tetrafluoroethylene (TFE), a copolymer of hexafluoropropylene (HFP), a terpolymer of tetrafluoroethylene (TFE), or any combination thereof.
[0235] Embodiment 63. The copper clad laminate of embodiment 61, wherein the perfluoropolymer comprises polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), or any combination thereof.
[0236] Embodiment 64. The copper clad laminate of embodiment 61, wherein the perfluoropolymer is composed of polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), or any combination thereof.
[0237] Embodiment 65. The copper clad laminate of any one of embodiments 44, 45, and 46, wherein the content of the resin matrix component is at least about 45 volume %, based on the total volume of the polymeric core film.
[0238] Embodiment 66. The copper clad laminate of any one of embodiments 44, 45, and 46, wherein the content of the resin matrix component is about 63 volume % or less, based on the total volume of the polymeric core film.
[0239] Embodiment 67. The copper clad laminate of embodiment 61, wherein the perfluoropolymer content is at least about 45% by volume, based on the total volume of the polymeric core film.
[0240] Embodiment 68. The copper clad laminate of embodiment 61, wherein the perfluoropolymer content is about 63 volume % or less, based on the total volume of the polymeric core film.
[0241] Embodiment 69. The copper clad laminate of any one of embodiments 44, 45, and 46, wherein the content of the ceramic filler component is at least about 45 volume %, based on the total volume of the polymer-based core film.
[0242] Embodiment 70. The copper clad laminate of any one of embodiments 44, 45, and 46, wherein the content of the ceramic filler component is about 57 volume % or less, based on the total volume of the polymeric core film.
[0243] Embodiment 71. The copper clad laminate of any one of embodiments 44, 45, and 46, wherein the content of the first filler material is at least about 80 volume %, based on the total volume of the ceramic filler component.
[0244] Embodiment 72. The copper clad laminate of any one of embodiments 44, 45, and 46, wherein the content of the first filler material is about 100 volume % or less, based on the total volume of the ceramic filler component.
[0245] Embodiment 73. The copper clad laminate of any one of embodiments 44, 45, and 46, wherein the ceramic filler component further comprises a second filler material.
[0246] Embodiment 74. The copper clad laminate of embodiment 73, wherein the second filler material comprises a high dielectric constant ceramic material.
[0247] Embodiment 75. The copper clad laminate of embodiment 74, wherein the high dielectric constant ceramic material has a dielectric constant of at least about 14.
[0248] Embodiment 76. The copper clad laminate of embodiment 74, wherein the ceramic filler component further comprises TiO2, SrTiO3, ZrTi2O6, MgTiO3, CaTiO3, BaTiO4, or any combination thereof.
[0249] Embodiment 77. The copper clad laminate of embodiment 73, wherein the content of the second filler material is at least about 1 volume % based on the total volume of the ceramic filler component.
[0250] Embodiment 78. The copper clad laminate of embodiment 73, wherein the content of the second filler material is about 20 volume % or less, based on the total volume of the ceramic filler component.
[0251] Embodiment 79. The copper clad laminate of any one of embodiments 44, 45, and 46, wherein the ceramic filler component is at least about 97% amorphous.
[0252] Embodiment 80. The copper clad laminate of any one of embodiments 44, 45, and 46, wherein the polymeric core film comprises no more than about 10% by volume porosity.
[0253] Embodiment 81. The copper clad laminate of any one of embodiments 44, 45, and 46, wherein the polymeric core film comprises an average thickness of at least about 10 micrometers.
[0254] Embodiment 82. The copper clad laminate of any one of embodiments 44, 45, and 46, wherein the polymeric core film comprises an average thickness of about 2000 micrometers or less.
[0255] Embodiment 83. The copper clad laminate of any one of embodiments 44, 45, and 46, wherein the polymeric core film comprises a loss factor (5 GHz, 20% RH) of about 0.005 or less.
[0256] Embodiment 84. The copper clad laminate of any one of embodiments 44, 45, and 46, wherein the polymeric core film comprises a loss factor (5 GHz, 20% RH) of about 0.0014 or less.
[0257] Embodiment 85. The copper clad laminate of any one of embodiments 44, 45, and 46, wherein the polymeric core film comprises a coefficient of thermal expansion (all axes) of about 80 ppm / ° C. or less.
[0258] Embodiment 86. The copper clad laminate of any one of embodiments 44, 45, and 46, wherein the polymeric core film comprises a moisture absorption of about 0.05% or less.
[0259] Embodiment 87. The copper clad laminate of any one of embodiments 44, 45, and 46, wherein the copper clad laminate comprises a porosity of about 10% by volume or less.
[0260] Embodiment 88. The copper clad laminate of any one of embodiments 44, 45, and 46, wherein the copper clad laminate comprises a peel strength between the copper foil layer and the dielectric substrate of at least about 6 lb / in.
[0261] Embodiment 89. A printed circuit board including a copper clad laminate, the copper clad laminate including a copper foil layer and a dielectric substrate covering the copper foil layer, the dielectric substrate including a polymer-based core film and a fluoropolymer-based adhesive layer, the polymer-based core film including a resin matrix component and a ceramic filler component, the ceramic filler component including a first filler material, the particle size distribution of the first filler material being at least about 0.5 micrometers and no more than about 1.6 micrometers D 10 , D of at least about 0.8 micrometers and not more than about 2.7 micrometers 50 and D of at least about 1.5 micrometers and not more than about 4.7 micrometers 90 a printed circuit board comprising:
[0262] Embodiment 90. A printed circuit board comprising a copper clad laminate, the copper clad laminate comprising a copper foil layer and a dielectric substrate covering the copper foil layer, the dielectric substrate comprising a polymer-based core film and a fluoropolymer-based adhesive layer, the polymer-based core film comprising a resin matrix component and a ceramic filler component, the ceramic filler component comprising a first filler material, the first filler material further comprising an average particle size of about 10 micrometers or less and a particle size distribution span (PSDS) of about 5 or less, the PSDS being less than (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler material 90 D is equal to the particle size distribution measurement 10 is the D of the first filler material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler material 50 Printed circuit board, equal to particle size distribution measurements.
[0263] Embodiment 91. A printed circuit board including a copper clad laminate, the copper clad laminate including a copper foil layer and a dielectric substrate covering the copper foil layer, the dielectric substrate including a polymer-based core film and a fluoropolymer-based adhesive layer, the polymer-based core film including a resin matrix component and a ceramic filler component, the ceramic filler component including a first filler material, the first filler material including a ceramic filler having an average particle size of about 10 micrometers or less and an average particle size of about 8 micrometers or less. 2 The printed circuit board further comprises an average surface area of less than or equal to 100 nm / g.
[0264] Embodiment 92. The particle size distribution of the first filler material is at least about 0.5 micrometers and no more than about 1.6 micrometers D 10 92. The printed circuit board of embodiment 90 or 91, comprising:
[0265] Embodiment 93. The particle size distribution of the first filler material is at least about 0.8 micrometers and no more than about 2.7 micrometers D 50 92. The printed circuit board of embodiment 90 or 91, comprising:
[0266] Embodiment 94. The particle size distribution of the first filler material is at least about 1.5 micrometers and no greater than about 4.7 micrometers D 90 92. The printed circuit board of embodiment 90 or 91, comprising:
[0267] Embodiment 95. The printed circuit board of embodiment 89, wherein the first filler material further comprises an average particle size of about 10 micrometers or less.
[0268] Embodiment 96. The printed circuit board of any one of embodiments 89, 90, and 91, wherein the first filler material comprises an average particle size of about 10 micrometers or less.
[0269] Embodiment 97. The first filler material comprises a particle size distribution span (PSDS) of about 5 or less, the PSDS being (D 90 -D 10 ) / D 50 is equal to D 90is the D of the first filler material 90 D is equal to the particle size distribution measurement 10 is the D of the first filler material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler material 50 92. The printed circuit board of embodiment 89 or 91, wherein the particle size distribution measurement is equal.
[0270] Embodiment 98. The first filler material is about 8 m 2 91. The printed circuit board of embodiment 89 or 90, further comprising an average surface area of less than or equal to 1 / g.
[0271] Embodiment 99. A printed circuit board according to any one of embodiments 89, 90, and 91, wherein the fluoropolymer adhesive layer has an average thickness of at least about 0.2 micrometers.
[0272] Embodiment 100. A printed circuit board according to any one of embodiments 89, 90, and 91, wherein the fluoropolymer adhesive layer has an average thickness of about 7 micrometers or less.
[0273] Embodiment 101. The printed circuit board according to any one of embodiments 89, 90, and 91, wherein the fluoropolymer-based adhesive layer comprises a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene (mPTFE), copolymers and terpolymers of tetrafluoroethylene such as fluorinated ethylene-propylene (FEP), perfluoroalkoxy polymer resins (PFA), and modified perfluoroalkoxy polymer resins (mPFA), as well as derivatives and blends thereof. According to yet other embodiments, the fluoropolymer-based adhesive layer 207 may be composed of a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene.
[0274] Embodiment 102. The printed circuit board according to any one of embodiments 89, 90, and 91, wherein the fluoropolymer-based adhesive layer is made of a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene (mPTFE), copolymers and terpolymers of tetrafluoroethylene such as fluorinated ethylene-propylene (FEP), perfluoroalkoxy polymer resins (PFA), and modified perfluoroalkoxy polymer resins (mPFA), as well as derivatives and blends thereof. According to yet another embodiment, the fluoropolymer-based adhesive layer 207 may be made of a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene.
[0275] Embodiment 103. A printed circuit board according to any one of embodiments 89, 90, and 91, wherein the fluoropolymer adhesive layer is a PFA layer.
[0276] Embodiment 104. A printed circuit board according to any one of embodiments 89, 90, and 91, wherein the first filler material comprises a silica-based compound.
[0277] Embodiment 105. A printed circuit board according to any one of embodiments 89, 90, and 91, wherein the first filler material comprises silica.
[0278] Embodiment 106. A printed circuit board according to any one of embodiments 89, 90, and 91, wherein the resin matrix comprises a perfluoropolymer.
[0279] Embodiment 107. The printed circuit board of embodiment 106, wherein the perfluoropolymer comprises a copolymer of tetrafluoroethylene (TFE), a copolymer of hexafluoropropylene (HFP), a terpolymer of tetrafluoroethylene (TFE), or any combination thereof.
[0280] Embodiment 108. The printed circuit board of embodiment 106, wherein the perfluoropolymer comprises polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), or any combination thereof.
[0281] Embodiment 109. The printed circuit board of embodiment 106, wherein the perfluoropolymer is composed of polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), or any combination thereof.
[0282] Embodiment 110. The printed circuit board of any one of embodiments 89, 90, and 91, wherein the content of the resin matrix component is at least about 45 volume %, based on the total volume of the polymeric core film.
[0283] Embodiment 111. A printed circuit board according to any one of embodiments 89, 90, and 91, wherein the content of the resin matrix component is about 63 volume % or less, based on the total volume of the polymeric core film.
[0284] Embodiment 112. The printed circuit board of embodiment 106, wherein the perfluoropolymer content is at least about 45% by volume, based on the total volume of the polymer-based core film.
[0285] Embodiment 113. The printed circuit board of embodiment 106, wherein the perfluoropolymer content is about 63 volume % or less, based on the total volume of the polymer core film.
[0286] Embodiment 114. A printed circuit board according to any one of embodiments 89, 90, and 91, wherein the content of the ceramic filler component is at least about 45 volume percent, based on the total volume of the polymer-based core film.
[0287] Embodiment 115. A printed circuit board according to any one of embodiments 89, 90, and 91, wherein the content of the ceramic filler component is about 57 volume % or less, based on the total volume of the polymer-based core film.
[0288] Embodiment 116. A printed circuit board according to any one of embodiments 89, 90, and 91, wherein the content of the first filler material is at least about 80% by volume, based on the total volume of the ceramic filler component.
[0289] Embodiment 117. A printed circuit board according to any one of embodiments 89, 90, and 91, wherein the content of the first filler material is about 100% by volume or less, based on the total volume of the ceramic filler component.
[0290] Embodiment 118. The printed circuit board of any one of embodiments 89, 90, and 91, wherein the ceramic filler component further comprises a second filler material.
[0291] Embodiment 119. The printed circuit board of embodiment 118, wherein the second filler material comprises a high dielectric constant ceramic material.
[0292] Embodiment 120. The printed circuit board of embodiment 119, wherein the high dielectric constant ceramic material has a dielectric constant of at least about 14.
[0293] Embodiment 121. The printed circuit board of embodiment 119, wherein the ceramic filler component further comprises TiO2, SrTiO3, ZrTi2O6, MgTiO3, CaTiO3, BaTiO4, or any combination thereof.
[0294] Embodiment 122. The printed circuit board of embodiment 118, wherein the content of the second filler material is at least about 1 volume percent, based on the total volume of the ceramic filler component.
[0295] Embodiment 123. The printed circuit board of embodiment 118, wherein the content of the second filler material is about 20 volume % or less, based on the total volume of the ceramic filler component.
[0296] Embodiment 124. The printed circuit board of any one of embodiments 89, 90, and 91, wherein the ceramic filler component is at least about 97% amorphous.
[0297] Embodiment 125. A printed circuit board according to any one of embodiments 89, 90, and 91, wherein the polymer-based core film comprises a porosity of about 10% by volume or less.
[0298] Embodiment 126. A printed circuit board according to any one of embodiments 89, 90, and 91, wherein the polymer-based core film comprises an average thickness of at least about 10 micrometers.
[0299] Embodiment 127. A printed circuit board according to any one of embodiments 89, 90, and 91, wherein the polymer-based core film comprises an average thickness of about 2000 micrometers or less.
[0300] Embodiment 128. A printed circuit board according to any one of embodiments 89, 90, and 91, wherein the polymer-based core film comprises a loss factor (5 GHz, 20% RH) of about 0.005 or less.
[0301] Embodiment 129. A printed circuit board as described in any one of embodiments 89, 90, and 91, wherein the polymer-based core film comprises a loss factor (5 GHz, 20% RH) of about 0.0014 or less.
[0302] Embodiment 130. The printed circuit board of any one of embodiments 89, 90, and 91, wherein the polymer-based core film comprises a coefficient of thermal expansion (all axes) of about 80 ppm / °C or less.
[0303] Embodiment 131. The printed circuit board of any one of embodiments 89, 90, and 91, wherein the polymer-based core film has a moisture absorption of about 0.05% or less.
[0304] Embodiment 132. A printed circuit board according to any one of embodiments 89, 90, and 91, wherein the copper clad laminate comprises a porosity of about 10% by volume or less.
[0305] Embodiment 133. The printed circuit board of any one of embodiments 89, 90, and 91, wherein the copper clad laminate comprises a peel strength between the copper foil layer and the printed circuit board of at least about 6 lb / in.
[0306] Embodiment 134. A method of forming a dielectric substrate, the method comprising: combining a resin matrix precursor component and a ceramic filler precursor component to form a forming mixture; forming the forming mixture into a polymer-based core film; and coating the polymer-based core film with a fluoropolymer-based adhesive layer, the ceramic filler precursor component comprising a first filler precursor material, the first filler precursor material having a particle size distribution of at least about 0.5 micrometers and a D of no greater than about 1.6. 10 , D of at least about 0.8 micrometers and not more than about 2.7 micrometers 50 and D of at least about 1.5 micrometers and not more than about 4.7 micrometers 90 A method comprising:
[0307] Embodiment 135. A method of forming a dielectric substrate, the method comprising: combining a resin precursor matrix component and a ceramic filler precursor component to form a forming mixture; forming the forming mixture into a polymeric core film; and coating the polymeric core film with a fluoropolymer adhesive layer, the ceramic filler precursor component comprising a first filler precursor material, the first filler precursor material further comprising an average particle size of about 10 micrometers or less and a particle size distribution span (PSDS) of about 5 or less, the PSDS being greater than or equal to (D 90 -D 10 ) / D50 is equal to D 90 is the D of the first filler precursor material 90 D is equal to the particle size distribution measurement 10 is the D of the first filler precursor material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler precursor material 50 Equivalent to particle size distribution measurement, method.
[0308] Embodiment 136. A method of forming a dielectric substrate, the method comprising: combining a resin matrix precursor component and a ceramic filler precursor component to form a forming mixture; forming the forming mixture into a polymer-based core film; and coating the polymer-based core film with a fluoropolymer-based adhesive layer, the ceramic filler precursor component comprising a first filler precursor material having an average particle size of about 10 micrometers or less and an average particle size of about 8 micrometers or less. 2 / g or less.
[0309] Embodiment 137. The particle size distribution of the first filler precursor material is at least about 0.5 micrometers and no greater than about 1.6 micrometers D 10 137. The method of embodiment 135 or 136, comprising:
[0310] Embodiment 138. The particle size distribution of the first filler precursor material is at least about 0.8 micrometers and no greater than about 2.7 micrometers D 50 137. The method of embodiment 135 or 136, comprising:
[0311] Embodiment 139. The particle size distribution of the first filler precursor material is at least about 1.5 micrometers and no greater than about 4.7 micrometers D 90 137. The method of embodiment 135 or 136, comprising:
[0312] Embodiment 140. The method of embodiment 134, wherein the first filler precursor material further comprises an average particle size of about 10 micrometers or less.
[0313] Embodiment 141. The method of any one of embodiments 135, 136, and 140, wherein the first filler precursor material comprises an average particle size of about 10 micrometers or less.
[0314] Embodiment 142. A first filler precursor material comprises a particle size distribution span (PSDS) of about 5 or less, the PSDS being (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler precursor material 90 D is equal to the particle size distribution measurement 10 is the D of the first filler precursor material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler precursor material 50 The method of any one of embodiments 134 and 136, wherein the particle size distribution measurement is equivalent to the particle size distribution measurement.
[0315] Embodiment 143. The first filler precursor material is about 8 m 2 136. The method of embodiment 134 or 135, further comprising an average surface area of less than or equal to 1 / g.
[0316] Embodiment 144. The method of any one of embodiments 134, 135, and 136, wherein the fluoropolymer adhesive layer has an average thickness of at least about 0.2 micrometers.
[0317] Embodiment 145. The method of any one of embodiments 134, 135, and 136, wherein the fluoropolymer adhesive layer has an average thickness of about 7 micrometers or less.
[0318] Embodiment 146. The method of any one of embodiments 134, 135, and 136, wherein the fluoropolymer-based adhesive layer comprises a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene (mPTFE), copolymers and terpolymers of tetrafluoroethylene such as fluorinated ethylene-propylene (FEP), perfluoroalkoxy polymer resins (PFA), and modified perfluoroalkoxy polymer resins (mPFA), and derivatives and blends thereof. According to yet other embodiments, the fluoropolymer-based adhesive layer 207 may be composed of a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene.
[0319] Embodiment 147. The method of any one of embodiments 134, 135, and 136, wherein the fluoropolymer-based adhesive layer is composed of a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene (mPTFE), copolymers and terpolymers of tetrafluoroethylene such as fluorinated ethylene-propylene (FEP), perfluoroalkoxy polymer resins (PFA), and modified perfluoroalkoxy polymer resins (mPFA), and derivatives and blends thereof. According to yet other embodiments, the fluoropolymer-based adhesive layer 207 may be composed of a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene.
[0320] Embodiment 148. The method of any one of embodiments 134, 135, and 136, wherein the fluoropolymer adhesive layer is a PFA layer.
[0321] Embodiment 149. The method of any one of embodiments 134, 135, and 136, wherein the first filler precursor material comprises a silica-based compound.
[0322] Embodiment 150. The method of any one of embodiments 134, 135, and 136, wherein the first filler precursor material comprises silica.
[0323] Embodiment 151. The method of any one of embodiments 134, 135, and 136, wherein the resin matrix precursor component comprises a perfluoropolymer.
[0324] Embodiment 152. The method of embodiment 151, wherein the perfluoropolymer comprises a copolymer of tetrafluoroethylene (TFE), a copolymer of hexafluoropropylene (HFP), a terpolymer of tetrafluoroethylene (TFE), or any combination thereof.
[0325] Embodiment 153. The method of embodiment 151, wherein the perfluoropolymer comprises polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), or any combination thereof.
[0326] Embodiment 154. The method of embodiment 151, wherein the perfluoropolymer is comprised of polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), or any combination thereof.
[0327] Embodiment 155. The content of the resin matrix precursor component, according to any one of embodiments 134, 135, and 136.
[0328] Embodiment 156. The method of any one of embodiments 134, 135, and 136, wherein the content of the resin matrix precursor component is about 63 volume % or less, based on the total volume of the forming mixture.
[0329] Embodiment 157. The method of embodiment 151, wherein the perfluoropolymer content is at least about 45% by volume, based on the total volume of the forming mixture.
[0330] Embodiment 158. The method of embodiment 151, wherein the perfluoropolymer content is about 63% by volume or less, based on the total volume of the forming mixture.
[0331] Embodiment 159. The method of any one of embodiments 134, 135, and 136, wherein the content of the ceramic filler precursor component is at least about 45 volume percent, based on the total volume of the forming mixture.
[0332] Embodiment 160. The method of any one of embodiments 134, 135, and 136, wherein the content of the ceramic filler precursor component is about 57 volume percent or less, based on the total volume of the forming mixture.
[0333] Embodiment 161. The method of any one of embodiments 134, 135, and 136, wherein the content of the first filler precursor material is at least about 80 volume %, based on the total volume of the ceramic filler precursor components.
[0334] Embodiment 162. The method of any one of embodiments 134, 135, and 136, wherein the content of the first filler precursor material is about 100 volume % or less, based on the total volume of the ceramic filler precursor components.
[0335] Embodiment 163. The method of any one of embodiments 134, 135, and 136, wherein the ceramic filler precursor component further comprises a second filler precursor material.
[0336] Embodiment 164. The method of embodiment 163, wherein the second filler precursor material comprises a high dielectric constant ceramic material.
[0337] Embodiment 165. The method of embodiment 164, wherein the high dielectric constant ceramic material has a dielectric constant of at least about 14.
[0338] Embodiment 166. The method of embodiment 164, wherein the ceramic filler precursor component further comprises TiO2, SrTiO3, ZrTi2O6, MgTiO3, CaTiO3, BaTiO4, or any combination thereof.
[0339] Embodiment 167. The method of embodiment 163, wherein the content of the second filler precursor material is at least about 1 vol. %, based on the total volume of the ceramic filler precursor components.
[0340] Embodiment 168. The method of embodiment 163, wherein the content of the second filler precursor material is about 20 volume % or less, based on the total volume of the ceramic filler precursor components.
[0341] Embodiment 169. The method of any one of embodiments 134, 135, and 136, wherein the ceramic filler precursor component is at least about 97% amorphous.
[0342] Embodiment 170. The method of any one of embodiments 134, 135, and 136, wherein the polymer-based core film comprises no more than about 10% by volume porosity.
[0343] Embodiment 171. The method of any one of embodiments 134, 135, and 136, wherein the polymer-based core film comprises an average thickness of at least about 10 micrometers.
[0344] Embodiment 172. The method of any one of embodiments 134, 135, and 136, wherein the polymer-based core film comprises an average thickness of about 2000 micrometers or less.
[0345] Embodiment 173. The method of any one of embodiments 134, 135, and 136, wherein the polymer-based core film comprises a loss factor (5 GHz, 20% RH) of about 0.005 or less.
[0346] Embodiment 174. The method of any one of embodiments 134, 135, and 136, wherein the polymer-based core film comprises a loss factor (5 GHz, 20% RH) of about 0.0014 or less.
[0347] Embodiment 175. The method of any one of embodiments 134, 135, and 136, wherein the polymer-based core film comprises a coefficient of thermal expansion (all axes) of about 80 ppm / °C or less.
[0348] Embodiment 176. The method of any one of embodiments 134, 135, and 136, wherein the polymer-based core film comprises a moisture absorption of about 0.05% or less.
[0349] Embodiment 177. A method of forming a copper clad laminate, the method comprising: providing a copper foil layer; combining a resin matrix precursor component and a ceramic filler precursor component to form a forming mixture; forming the forming mixture into a polymer-based core film; and providing a fluoropolymer-based adhesive layer between the polymer-based core film and the copper foil layer, wherein the ceramic filler precursor component comprises a first filler precursor material, and the first filler precursor material has a particle size distribution of at least about 0.5 micrometers and a D of no greater than about 1.6. 10 , D of at least about 0.8 micrometers and not more than about 2.7 micrometers 50 and D of at least about 1.5 micrometers and not more than about 4.7 micrometers 90 A method comprising:
[0350] Embodiment 178. A method of forming a copper clad laminate, the method comprising: providing a copper foil layer; combining a resin matrix precursor component and a ceramic filler precursor component to form a forming mixture; forming the forming mixture into a polymeric core film; and providing a fluoropolymer adhesive layer between the polymeric core film and the copper foil layer, the ceramic filler precursor component comprising a first filler precursor material, the first filler precursor material further comprising an average particle size of about 10 micrometers or less and a particle size distribution span (PSDS) of about 5 or less, the PSDS being greater than or equal to (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler precursor material 90 D is equal to the particle size distribution measurement 10 is the D of the first filler precursor material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler precursor material 50 Equivalent to particle size distribution measurement, method.
[0351] Embodiment 179. A method of forming a copper clad laminate, the method comprising: providing a copper foil layer; combining a resin matrix precursor component and a ceramic filler precursor component to form a forming mixture; forming the forming mixture into a polymeric core film; and providing a fluoropolymer adhesive layer between the polymeric core film and the copper foil layer, the ceramic filler precursor component comprising a first filler precursor material having an average particle size of about 10 micrometers or less and an average particle size of about 8 micrometers or less. 2 / g or less.
[0352] Embodiment 180. The particle size distribution of the first filler precursor material is at least about 0.5 micrometers and no greater than about 1.6 micrometers D 10 179. The method of claim 178 or 179, comprising:
[0353] Embodiment 181. The particle size distribution of the first filler precursor material is at least about 0.8 micrometers and no greater than about 2.7 micrometers D 50 179. The method of claim 178 or 179, comprising:
[0354] Embodiment 182. The particle size distribution of the first filler precursor material is at least about 1.5 micrometers and no greater than about 4.7 micrometers D 90 179. The method of claim 178 or 179, comprising:
[0355] Embodiment 183. The method of embodiment 182, wherein the first filler precursor material further comprises an average particle size of about 10 micrometers or less.
[0356] Embodiment 184. The method of any one of embodiments 177, 178, and 179, wherein the first filler precursor material comprises an average particle size of about 10 micrometers or less.
[0357] Embodiment 185. A first filler precursor material comprises a particle size distribution span (PSDS) of about 5 or less, the PSDS being (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler precursor material 90 D is equal to the particle size distribution measurement 10 is the D of the first filler precursor material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler precursor material 50 180. The method of embodiment 177 or 179, wherein the particle size distribution measurement is equivalent to the particle size distribution measurement.
[0358] Embodiment 186. The first filler precursor material is about 8 m 2 180. The method of embodiment 177 or 179, further comprising an average surface area of less than or equal to 1 / g.
[0359] Embodiment 187. The method of any one of embodiments 177, 178, and 179, wherein the fluoropolymer adhesive layer has an average thickness of at least about 0.2 micrometers.
[0360] Embodiment 188. The method of any one of embodiments 177, 178, and 179, wherein the fluoropolymer adhesive layer has an average thickness of about 7 micrometers or less.
[0361] Embodiment 189. The method of any one of embodiments 177, 178, and 179, wherein the fluoropolymer-based adhesive layer comprises a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene (mPTFE), copolymers and terpolymers of tetrafluoroethylene such as fluorinated ethylene-propylene (FEP), perfluoroalkoxy polymer resins (PFA), and modified perfluoroalkoxy polymer resins (mPFA), and derivatives and blends thereof. According to yet other embodiments, the fluoropolymer-based adhesive layer 207 may be composed of a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene.
[0362] Embodiment 190. The method of any one of embodiments 177, 178, and 179, wherein the fluoropolymer-based adhesive layer is composed of a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene (mPTFE), copolymers and terpolymers of tetrafluoroethylene such as fluorinated ethylene-propylene (FEP), perfluoroalkoxy polymer resins (PFA), and modified perfluoroalkoxy polymer resins (mPFA), and derivatives and blends thereof. According to yet other embodiments, the fluoropolymer-based adhesive layer 207 may be composed of a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene.
[0363] Embodiment 191. The method of any one of embodiments 177, 178, and 179, wherein the fluoropolymer adhesive layer is a PFA layer.
[0364] Embodiment 192. The method of any one of embodiments 177, 178, and 179, wherein the first filler precursor material comprises a silica-based compound.
[0365] Embodiment 193. The method of any one of embodiments 177, 178, and 179, wherein the first filler precursor material comprises silica.
[0366] Embodiment 194. The method of any one of embodiments 177, 178, and 179, wherein the resin matrix comprises a perfluoropolymer.
[0367] Embodiment 195. The method of embodiment 194, wherein the perfluoropolymer comprises a copolymer of tetrafluoroethylene (TFE), a copolymer of hexafluoropropylene (HFP), a terpolymer of tetrafluoroethylene (TFE), or any combination thereof.
[0368] Embodiment 196. The method of embodiment 194, wherein the perfluoropolymer comprises polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), or any combination thereof.
[0369] Embodiment 197. The method of embodiment 194, wherein the perfluoropolymer is comprised of polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), or any combination thereof.
[0370] Embodiment 198. The method of any one of embodiments 177, 178, and 179, wherein the content of the resin matrix precursor component is at least about 45 volume percent, based on the total volume of the polymeric core film.
[0371] Embodiment 199. The method of any one of embodiments 177, 178, and 179, wherein the content of the resin matrix precursor component is about 63 volume % or less, based on the total volume of the polymeric core film.
[0372] Embodiment 200. The method of embodiment 194, wherein the perfluoropolymer content is at least about 45% by volume, based on the total volume of the polymeric core film.
[0373] Embodiment 201. The method of embodiment 194, wherein the perfluoropolymer content is about 63 volume % or less, based on the total volume of the polymeric core film.
[0374] Embodiment 202. The method of any one of embodiments 177, 178, and 179, wherein the content of the ceramic filler precursor component is at least about 45 volume percent, based on the total volume of the polymeric core film.
[0375] Embodiment 203. The method of any one of embodiments 177, 178, and 179, wherein the content of the ceramic filler precursor component is about 57 volume % or less, based on the total volume of the polymeric core film.
[0376] Embodiment 204. The method of any one of embodiments 177, 178, and 179, wherein the content of the first filler precursor material is at least about 80 volume percent, based on the total volume of the ceramic filler precursor components.
[0377] Embodiment 205. The method of any one of embodiments 177, 178, and 179, wherein the content of the first filler precursor material is about 100 volume % or less, based on the total volume of the ceramic filler precursor components.
[0378] Embodiment 206. The method of any one of embodiments 177, 178, and 179, wherein the ceramic filler precursor component further comprises a second filler material.
[0379] Embodiment 207. The method of embodiment 194, wherein the second filler material comprises a high dielectric constant ceramic material.
[0380] Embodiment 208. The method of embodiment 195, wherein the high dielectric constant ceramic material has a dielectric constant of at least about 14.
[0381] Embodiment 209. The method of embodiment 195, wherein the ceramic filler precursor component further comprises TiO2, SrTiO3, ZrTi2O6, MgTiO3, CaTiO3, BaTiO4, or any combination thereof.
[0382] Embodiment 210. The method of embodiment 194, wherein the content of the second filler material is at least about 1 vol. %, based on the total volume of the ceramic filler precursor components.
[0383] Embodiment 211. The method of embodiment 194, wherein the content of the second filler material is about 20 volume % or less, based on the total volume of the ceramic filler precursor components.
[0384] Embodiment 212. The method of any one of embodiments 177, 178, and 179, wherein the ceramic filler precursor component is at least about 97% amorphous.
[0385] Embodiment 213. The method of any one of embodiments 177, 178, and 179, wherein the polymer-based core film comprises no more than about 10% by volume porosity.
[0386] Embodiment 214. The method of any one of embodiments 177, 178, and 179, wherein the polymer-based core film comprises an average thickness of at least about 10 micrometers.
[0387] Embodiment 215. The method of any one of embodiments 177, 178, and 179, wherein the polymer-based core film comprises an average thickness of about 2000 micrometers or less.
[0388] Embodiment 216. The method of any one of embodiments 177, 178, and 179, wherein the polymer-based core film comprises a loss factor (5 GHz, 20% RH) of about 0.005 or less.
[0389] Embodiment 217. The method of any one of embodiments 177, 178, and 179, wherein the polymer-based core film comprises a loss factor (5 GHz, 20% RH) of about 0.0014 or less.
[0390] Embodiment 218. The method of any one of embodiments 177, 178, and 179, wherein the polymer-based core film comprises a coefficient of thermal expansion (all axes) of about 80 ppm / °C or less.
[0391] Embodiment 219. The method of any one of embodiments 177, 178, and 179, wherein the polymer-based core film comprises a moisture absorption of about 0.05% or less.
[0392] Embodiment 220. The method of any one of embodiments 177, 178, and 179, wherein the copper clad laminate comprises no more than about 10% by volume porosity.
[0393] Embodiment 221. The method of any one of embodiments 177, 178, and 179, wherein the copper clad laminate comprises a peel strength between the copper foil layer and the dielectric substrate of at least about 6 lb / in.
[0394] Embodiment 222. A method of forming a printed circuit board, the method comprising: providing a copper foil layer; combining a resin matrix precursor component and a ceramic filler precursor component to form a forming mixture; forming the forming mixture into a polymeric core film; and providing a fluoropolymer adhesive layer between the polymeric core film and the copper foil layer, the ceramic filler precursor component comprising a first filler precursor material, the first filler precursor material having a particle size distribution of at least about 0.5 micrometers and no greater than about 1.6 D. 10 , D of at least about 0.8 micrometers and not more than about 2.7 micrometers 50 and D of at least about 1.5 micrometers and not more than about 4.7 micrometers 90 A method comprising:
[0395] Embodiment 223. A method of forming a printed circuit board, the method comprising: providing a copper foil layer; combining a resin matrix precursor component and a ceramic filler precursor component to form a forming mixture; forming the forming mixture into a polymeric core film; and providing a fluoropolymer adhesive layer between the polymeric core film and the copper foil layer, the ceramic filler precursor component comprising a first filler precursor material, the first filler precursor material further comprising an average particle size of about 10 micrometers or less and a particle size distribution span (PSDS) of about 5 or less, the PSDS being greater than or equal to (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler precursor material 90 D is equal to the particle size distribution measurement 10is the D of the first filler precursor material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler precursor material 50 Equivalent to particle size distribution measurement, method.
[0396] Embodiment 224. A method of forming a printed circuit board, the method comprising: providing a copper foil layer; combining a resin matrix precursor component and a ceramic filler precursor component to form a forming mixture; forming the forming mixture into a polymeric core film; and providing a fluoropolymer adhesive layer between the polymeric core film and the copper foil layer, the ceramic filler precursor component comprising a first filler precursor material having an average particle size of about 10 micrometers or less and a fluoropolymer-based adhesive layer having an average particle size of about 8 micrometers or less. 2 / g or less.
[0397] Embodiment 225. The particle size distribution of the first filler precursor material is at least about 0.5 micrometers and no greater than about 1.6 micrometers D 10 The method of embodiment 223 or 224, comprising:
[0398] Embodiment 226. The particle size distribution of the first filler precursor material is at least about 0.8 micrometers and no greater than about 2.7 micrometers D 50 The method of embodiment 223 or 224, comprising:
[0399] Embodiment 227. The particle size distribution of the first filler precursor material is at least about 1.5 micrometers and no greater than about 4.7 micrometers D 90 The method of embodiment 223 or 224, comprising:
[0400] Embodiment 228. The method of embodiment 227, wherein the first filler precursor material further comprises an average particle size of about 10 micrometers or less.
[0401] Embodiment 229. The method of any one of embodiments 222, 223, and 224, wherein the first filler precursor material comprises an average particle size of about 10 micrometers or less.
[0402] Embodiment 230. A first filler precursor material comprises a particle size distribution span (PSDS) of about 5 or less, the PSDS being (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler precursor material 90 D is equal to the particle size distribution measurement 10 is the D of the first filler precursor material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler precursor material 50 The method of embodiment 222 or 224, wherein the particle size distribution measurement is equivalent.
[0403] Embodiment 231. The first filler precursor material is about 8 m 2 225. The method of embodiment 222 or 224, further comprising an average surface area of less than or equal to 1 / g.
[0404] Embodiment 232. The method of any one of embodiments 222, 223, and 224, wherein the fluoropolymer adhesive layer has an average thickness of at least about 0.2 micrometers.
[0405] Embodiment 233. The method of any one of embodiments 222, 223, and 224, wherein the fluoropolymer adhesive layer has an average thickness of about 7 micrometers or less.
[0406] Embodiment 234. The method of any one of embodiments 222, 223, and 224, wherein the fluoropolymer-based adhesive layer comprises a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene (mPTFE), copolymers and terpolymers of tetrafluoroethylene such as fluorinated ethylene-propylene (FEP), perfluoroalkoxy polymer resins (PFA), and modified perfluoroalkoxy polymer resins (mPFA), and derivatives and blends thereof. According to yet other embodiments, the fluoropolymer-based adhesive layer 207 may be composed of a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene.
[0407] Embodiment 235. The method of any one of embodiments 222, 223, and 224, wherein the fluoropolymer-based adhesive layer is composed of a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene (mPTFE), copolymers and terpolymers of tetrafluoroethylene such as fluorinated ethylene-propylene (FEP), perfluoroalkoxy polymer resins (PFA), and modified perfluoroalkoxy polymer resins (mPFA), and derivatives and blends thereof. According to yet other embodiments, the fluoropolymer-based adhesive layer 207 may be composed of a fluoropolymer (e.g., polytetrafluoroethylene (PTFE), modified polytetrafluoroethylene.
[0408] Embodiment 236. The method of any one of embodiments 222, 223, and 224, wherein the fluoropolymer adhesive layer is a PFA layer.
[0409] Embodiment 237. The method of any one of embodiments 222, 223, and 224, wherein the first filler precursor material comprises a silica-based compound.
[0410] Embodiment 238. The method of any one of embodiments 222, 223, and 224, wherein the first filler precursor material comprises silica.
[0411] Embodiment 239. The method of any one of embodiments 222, 223, and 224, wherein the resin matrix comprises a perfluoropolymer.
[0412] Embodiment 240. The method of embodiment 239, wherein the perfluoropolymer comprises a copolymer of tetrafluoroethylene (TFE), a copolymer of hexafluoropropylene (HFP), a terpolymer of tetrafluoroethylene (TFE), or any combination thereof.
[0413] Embodiment 241. The method of embodiment 239, wherein the perfluoropolymer comprises polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), or any combination thereof.
[0414] Embodiment 242. The method of embodiment 239, wherein the perfluoropolymer is comprised of polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), or any combination thereof.
[0415] Embodiment 243. The method of any one of embodiments 222, 223, and 224, wherein the content of the resin matrix precursor component is at least about 45 volume percent, based on the total volume of the polymeric core film.
[0416] Embodiment 244. The method of any one of embodiments 222, 223, and 224, wherein the content of the resin matrix precursor component is about 63 volume % or less, based on the total volume of the polymeric core film.
[0417] Embodiment 245. The method of embodiment 239, wherein the perfluoropolymer content is at least about 45% by volume, based on the total volume of the polymeric core film.
[0418] Embodiment 246. The method of embodiment 239, wherein the perfluoropolymer content is about 63 volume % or less, based on the total volume of the polymeric core film.
[0419] Embodiment 247. The method of any one of embodiments 222, 223, and 224, wherein the content of the ceramic filler precursor component is at least about 45 volume percent, based on the total volume of the polymer-based core film.
[0420] Embodiment 248. The method of any one of embodiments 222, 223, and 224, wherein the content of the ceramic filler precursor component is about 57 volume % or less, based on the total volume of the polymeric core film.
[0421] Embodiment 249. The method of any one of embodiments 222, 223, and 224, wherein the content of the first filler precursor material is at least about 80 volume percent, based on the total volume of the ceramic filler precursor components.
[0422] Embodiment 250. The method of any one of embodiments 222, 223, and 224, wherein the content of the first filler precursor material is about 100 volume % or less, based on the total volume of the ceramic filler precursor components.
[0423] Embodiment 251. The method of any one of embodiments 222, 223, and 224, wherein the ceramic filler precursor component further comprises a second filler material.
[0424] Embodiment 252. The method of embodiment 239, wherein the second filler material comprises a high dielectric constant ceramic material.
[0425] Embodiment 253. The method of embodiment 240, wherein the high dielectric constant ceramic material has a dielectric constant of at least about 14.
[0426] Embodiment 254. The method of embodiment 240, wherein the ceramic filler precursor component further comprises TiO2, SrTiO3, ZrTi2O6, MgTiO3, CaTiO3, BaTiO4, or any combination thereof.
[0427] Embodiment 255. The method of embodiment 239, wherein the content of the second filler material is at least about 1% by volume, based on the total volume of the ceramic filler precursor components.
[0428] Embodiment 256. The method of embodiment 239, wherein the content of the second filler material is about 20 volume % or less, based on the total volume of the ceramic filler precursor components.
[0429] Embodiment 257. The method of any one of embodiments 222, 223, and 224, wherein the ceramic filler precursor component is at least about 97% amorphous.
[0430] Embodiment 258. The method of any one of embodiments 222, 223, and 224, wherein the polymer-based core film comprises no more than about 10% by volume porosity.
[0431] Embodiment 259. The method of any one of embodiments 222, 223, and 224, wherein the polymer-based core film comprises an average thickness of at least about 10 micrometers.
[0432] Embodiment 260. The method of any one of embodiments 222, 223, and 224, wherein the polymer-based core film comprises an average thickness of about 2000 micrometers or less.
[0433] Embodiment 261. The method of any one of embodiments 222, 223, and 224, wherein the polymer-based core film comprises a loss factor (5 GHz, 20% RH) of about 0.005 or less.
[0434] Embodiment 262. The method of any one of embodiments 222, 223, and 224, wherein the polymer-based core film comprises a loss factor (5 GHz, 20% RH) of about 0.0014 or less.
[0435] Embodiment 263. The method of any one of embodiments 222, 223, and 224, wherein the polymer-based core film comprises a coefficient of thermal expansion (all axes) of about 80 ppm / ° C. or less.
[0436] Embodiment 264. The method of any one of embodiments 222, 223, and 224, wherein the polymer-based core film comprises a moisture absorption of about 0.05% or less.
[0437] Embodiment 265. The method of any one of embodiments 222, 223, and 224, wherein the copper clad laminate comprises no more than about 10% by volume porosity.
[0438] Embodiment 266. The method of any one of embodiments 222, 223, and 224, wherein the copper clad laminate comprises a peel strength between the copper foil layer and the dielectric substrate of at least about 6 lb / in. EXAMPLES
[0439] The concepts described herein are further described in the following examples, which do not limit the scope of the invention described in the claims.
[0440] Example 1 Sample dielectric substrates S1-S12 were constructed and formed in accordance with certain embodiments described herein.
[0441] Each sample dielectric substrate was formed using a cast film process. In this process, a polyimide carrier belt pretreated with a fluoropolymer passes through a dip pan containing an aqueous forming mixture (i.e., a combination of the resin matrix component and the ceramic filler component) at the base of a coating tower. The coated carrier belt then passes through a metering zone where a metering bar removes excess dispersion from the coated carrier belt. After the metering zone, the coated carrier belt passes through a drying zone maintained at a temperature of 82°C to 121°C to evaporate water. The coated carrier belt with the dried film then passes through a bake zone maintained at a temperature of 315°C to 343°C. Finally, the carrier belt passes through a melting zone maintained at a temperature of 349°C to 399°C to sinter, i.e., coalesce, the resin matrix material. The coated carrier belt then passes through a cooling plenum from which it can be directed either to a subsequent dip pan or to a stripping device to begin the formation of additional layers of film. Once the desired film thickness is achieved, the film is peeled off the carrier belt.
[0442] The resin matrix component of each of the sample dielectric substrates S1 to S12 is polytetrafluoroethylene (PTFE). Further configuration and composition details of each of the dielectric substrates S1 to S12 are summarized in Table 1 below.
[0443] [Table 1]
[0444] Measured particle size distributions (i.e., D 10 , D 50 , and D 90 ), particle size distribution span, average particle size, and BET surface area are summarized in Table 2 below.
[0445] [Table 2]
[0446] The performance characteristics of each sample dielectric substrate S1-S12 are summarized below in Table 3. The summarized performance characteristics include the dielectric constant of the sample dielectric substrate measured at 5 GHz ("Dk(5 GHz)"), the loss factor of the substrate measured at 5 GHz at 20% RH ("Df(5 GHz, 20% RH)"), the loss factor of the sample dielectric substrate measured at 5 GHz at 80% RH ("Df(5 GHz, 80% RH)"), and the coefficient of thermal expansion ("CTE") of the sample dielectric substrate.
[0447] [Table 3]
[0448] Example 2 For comparison purposes, comparative sample dielectric substrates CS1 to CS10 were constructed and formed.
[0449] Each comparative sample dielectric substrate was formed using a cast film process. In this process, a polyimide carrier belt pretreated with a fluoropolymer passes through a dip pan containing an aqueous forming mixture (i.e., a combination of the resin matrix component and the ceramic filler component) at the base of a coating tower. The coated carrier belt then passes through a metering zone where a metering bar removes excess dispersion from the coated carrier belt. After the metering zone, the coated carrier belt passes through a drying zone maintained at a temperature of 82°C to 121°C to evaporate water. The coated carrier belt with the dried film then passes through a bake zone maintained at a temperature of 315°C to 343°C. Finally, the carrier belt passes through a melting zone maintained at a temperature of 349°C to 399°C to sinter, i.e., coalesce, the resin matrix material. The coated carrier belt then passes through a cooling plenum from which it can be directed either to a subsequent dip pan or to a stripping device to begin forming additional layers of film. Once the desired film thickness is achieved, the film is peeled from the carrier belt.
[0450] The resin matrix component of each of the comparative sample dielectric substrates CS1 to CS10 is polytetrafluoroethylene (PTFE). Further details of the configuration and composition of each of the dielectric substrates CS1 to CS10 are summarized in Table 4 below.
[0451] [Table 4]
[0452] Measured particle size distributions (i.e., D 10 , D 50 , and D 90 ), particle size distribution span, average particle size, and BET surface area are summarized in Table 2 below.
[0453] [Table 5]
[0454] The performance characteristics of each sample dielectric substrate CS1-S9 are summarized below in Table 6. The summarized performance characteristics include the dielectric constant of the sample dielectric substrate measured at 5 GHz ("Dk(5 GHz)"), the loss factor of the substrate measured at 5 GHz at 20% RH ("Df(5 GHz, 20% RH)"), the loss factor of the sample dielectric substrate measured at 5 GHz at 80% RH ("Df(5 GHz, 80% RH)"), and the coefficient of thermal expansion ("CTE") of the sample dielectric substrate.
[0455] [Table 6]
[0456] Example 3 Sample dielectric substrates S13-S28 were constructed and formed in accordance with certain embodiments described herein.
[0457] Each sample dielectric substrate was formed using a cast film process. In this process, a polyimide carrier belt pretreated with a fluoropolymer passes through a dip pan containing an aqueous forming mixture (i.e., a combination of the resin matrix component and the ceramic filler component) at the base of a coating tower. The coated carrier belt then passes through a metering zone where a metering bar removes excess dispersion from the coated carrier belt. After the metering zone, the coated carrier belt passes through a drying zone maintained at a temperature of 82°C to 121°C to evaporate water. The coated carrier belt with the dried film then passes through a bake zone maintained at a temperature of 315°C to 343°C. Finally, the carrier belt passes through a melting zone maintained at a temperature of 349°C to 399°C to sinter, i.e., coalesce, the resin matrix material. The coated carrier belt then passes through a cooling plenum from which it can be directed either to a subsequent dip pan or to a stripping device to begin the formation of additional layers of film. Once the desired film thickness is achieved, the film is peeled off the carrier belt.
[0458] The resin matrix component of each of the sample dielectric substrates S13-S28 is polytetrafluoroethylene (PTFE). Further construction and composition details of each of the dielectric substrates S13-S28, including details regarding the type, thickness and percentage of the bonding layer, are summarized in Table 7 below.
[0459] [Table 7]
[0460] The measured particle size distributions (i.e., D 10 , D 50 , and D 90 ), particle size distribution span, average particle size, and BET surface area are summarized in Table 2 above.
[0461] The performance characteristics of each sample dielectric substrate S13-S28 are summarized below in Table 8. The summarized performance characteristics include the dielectric constant of the sample dielectric substrate measured at 5 GHz ("Dk(5 GHz)"), the loss factor of the substrate measured at 5 GHz at 20% RH ("Df(5 GHz, 20% RH)"), the loss factor of the sample dielectric substrate measured at 5 GHz at 80% RH ("Df(5 GHz, 80% RH)"), and the coefficient of thermal expansion ("CTE") of the sample dielectric substrate.
[0462] [Table 8]
[0463] It should be noted that in the general description or examples, not all of the activities described above are required, some of the specific activities may not be required, and one or more additional activities may be performed in addition to the activities described. Still further, the order in which the activities are listed is not necessarily the order in which they are performed.
[0464] Benefits, other advantages, and solutions to problems have been described above with respect to particular embodiments. However, the benefits, advantages, solutions to problems, and any features that may provide or make more prominent any benefit, advantage, or solution should not be construed as critical, necessary, or essential features of any or all of the claims.
[0465] The specification and drawings of the embodiments described herein are intended to provide a general understanding of the structure of the various embodiments. The specification and drawings are not intended to serve as an exhaustive and comprehensive description of all elements and features of the apparatus and systems that use the structures or methods described herein. Separate embodiments may be provided in combination in a single embodiment, and conversely, various features that are described in the context of a single embodiment for brevity may be provided separately or in any subcombination. Furthermore, references to values described in ranges include each and every value within that range. Many other embodiments may become apparent to those skilled in the art only after reading this specification. Other embodiments may be used and derived from this disclosure, such that structural substitutions, logical substitutions, or other changes may be made without departing from the scope of this disclosure. Thus, this disclosure should be considered as illustrative and not restrictive.
Claims
1. A dielectric substrate, A polymer-based core film; a fluoropolymer-based adhesive layer; The polymer-based core film is A resin matrix component; a ceramic filler component; the ceramic filler component comprises a first filler material; The particle size distribution of the first filler material is D of at least about 0.5 micrometers and no more than about 1.6 micrometers 10 and, D of at least about 0.8 micrometers and no more than about 2.7 micrometers 50 and, D of at least about 1.5 micrometers and no more than about 4.7 micrometers 90 and a dielectric substrate.
2. The dielectric substrate of claim 1 , wherein the first filler material further comprises an average particle size of about 10 micrometers or less.
3. The first filler material comprises a particle size distribution span (PSDS) of about 5 or less, the PSDS being (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler material 90 D is equal to the particle size distribution measurement 10 is the D of the first filler material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler material 50 The dielectric substrate of claim 1 , wherein the particle size distribution is equal to a particle size distribution measurement.
4. The first filler material is about 8 m 2 The dielectric substrate of claim 1 further comprising an average surface area of less than or equal to 1 / g.
5. The dielectric substrate of claim 1 , wherein the first filler material comprises a silica-based compound.
6. The dielectric substrate of claim 1 , wherein the resin matrix component comprises a perfluoropolymer.
7. 2. The dielectric substrate of claim 1, wherein the resin matrix component content is at least about 45 volume % and not more than about 63 volume % based on the total volume of the polymer-based core film.
8. 10. The dielectric substrate of claim 1, wherein the ceramic filler component is present in an amount of at least about 45 volume percent and no more than about 57 volume percent, based on the total volume of the polymer-based core film.
9. 2. The dielectric substrate of claim 1, wherein the content of the first filler material is at least about 80 volume percent and not more than about 100 volume percent, based on the total volume of the ceramic filler component.
10. The dielectric substrate of claim 1 , wherein the dielectric substrate comprises a loss factor (5 GHz, 20% RH) of about 0.005 or less.
11. A copper clad laminate comprising: A copper foil layer and a dielectric substrate covering the copper foil layer, The dielectric substrate is A polymer-based core film; a fluoropolymer-based adhesive layer; The polymer-based core film is A resin matrix component; a ceramic filler component; the ceramic filler component comprises a first filler material; The particle size distribution of the first filler material is D of at least about 0.5 micrometers and no more than about 1.6 micrometers 10 and, D of at least about 0.8 micrometers and no more than about 2.7 micrometers 50 and, D of at least about 1.5 micrometers and no more than about 4.7 micrometers 90 and a copper clad laminate.
12. 12. The copper clad laminate of claim 11, wherein the first filler material further comprises an average particle size of about 10 micrometers or less.
13. The first filler material comprises a particle size distribution span (PSDS) of about 5 or less, the PSDS being (D 90 -D 10 ) / D 50 is equal to D 90 is the D of the first filler material 90 D is equal to the particle size distribution measurement 10 is the D of the first filler material 10 D is equal to the particle size distribution measurement 50 is the D of the first filler material 50 The copper clad laminate of claim 11, wherein the particle size distribution measurement is equal to the particle size distribution measurement.
14. The first filler material is about 8 m 2 12. The copper clad laminate of claim 11, further comprising an average surface area of less than or equal to 1 / g.
15. 1. A printed circuit board comprising a copper clad laminate, the copper clad laminate comprising: A copper foil layer and a dielectric substrate covering the copper foil layer, The dielectric substrate is A polymer-based core film; a fluoropolymer-based adhesive layer; The polymer-based core film is A resin matrix component; a ceramic filler component; the ceramic filler component comprises a first filler material; The particle size distribution of the first filler material is D of at least about 0.5 micrometers and no more than about 1.6 micrometers 10 and, D of at least about 0.8 micrometers and no more than about 2.7 micrometers 50 and, D of at least about 1.5 micrometers and no more than about 4.7 micrometers 90 and a printed circuit board.
Citation Information
Patent Citations
Circuit board material of compounded fluoropolymer containing filler, and manufacture thereof
JP1994283831A
Thermosetting resin composition, prepreg, laminate and printed wiring board
JP2020084038A
Dielectric layer with improved thermal conductivity
JP2020507888A